Magnet-absorbed detrital magnetite from the western Qaidam Basin: Implications to Mars sample return missions - Qi-Tao Hu; Wen-Ping Liu; Qi-Zhi Yao; Shao-Bing Zhang; Wan-Cai Li; Sheng-Quan Fu; Yi-Liang Li; Gen-Tao Zhou (Icarus, 2026)

Porosity inversion and determination in gob unconsolidated materials based on acoustic signal response - Shuai-Jing Ren; Le-Xiang-Qian Zhang; Jun Deng; Jin-Rui Wang; Cai-Ping Wang; Yang Xiao; Fu-Ru Kang; Hai-Jian Li; Long-Hui Dou (Fuel, 2026)

DDRGK1 regulates muscle development by maintaining mitochondrial calcium homeostasis and oxidative phosphorylation via stabilizing IP3R - Ping Li; Lingfei Li; Mali Guo; Junjie Xu; Yafei Cai (Molecular Biology Reports, 2026)

Spoilage characteristics and mechanisms of dominant spoilage Bacteria in fresh beef stored at ice temperature: Insights from in situ analysis and metabolomics - Sunyan Wang; Kezhou Cai; Ping Li; Yang Wang; Zhijie Bao; Xiaoyu He; Wendi Zhang; Feiran Xu; Baocai Xu (Food Research International, 2026)

Highly selective CO2/H2 separation by isomeric CALF-20-based porous slurry - Han Tang; Jin Cai; Zi-Ying Zhao; Long-Long Xie; Ping-Xiang Wang; Yang Meng; Hai-Hang Qin; Peng Xiao; Bei Liu; Yun-Lei Peng; Chang-Yu Sun; Zhi Li; et al. (Chemical Engineering Journal, 2026)

Selective removal of fluoxetine by a core-shell molecularly imprinted TiO2 photocatalyst: degradation mechanism and toxicity mitigation - Ding Pan; Xin-Yi Jiao; Peng Liu; Jing-Hao Yang; Jing-Jun Qin; Cai-Shan Wang; Ying-Zhi Ding; Xue-Rong Wang; Yan-Chao Jin; Xin-Hui Liu; Zhang Liu; Li-Ping Li (Chemical Engineering Journal, 2026)

Phenethylamine modulates intestinal inflammation and barrier integrity in diarrhea-predominant irritable bowel syndrome through the TAAR1-PKC signaling pathway - Li Cai; Ping Chen; Weina Mou; Lu Zhang; Xiaoliang Li; Liwei Xue (Tissue and Cell, 2026)

Enhanced solar-driven interfacial vapor generation of lignite-based aerogel via water and thermal dual management - Mei Xiong; Hong-Lei Yan; Zhan-Ku Li; Wei-Dong Zhang; Jing-Chong Yan; Zhi-Ping Lei; Zhao Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui (Journal of Environmental Chemical Engineering, 2026)

Hierarchical core–shell nanoplatforms based on sacrificial template-directed ZnO2@ZIF-8 for spatiotemporally controlled and self-augmented chemodynamic–photothermal antibacterial therapy - Yi-Fei Hui; Duan-Ping Hu; Yi Zhao; Shulin Li; Zhi-Feng Cai; Lin-Yi Li; Yuming Xie; Yong-Nian Zeng; Zu-Jin Lin; Fa-Qiang Tang (Chemical Engineering Journal, 2026)

Isotopic compositions reveal distinct roles of in-cloud and below-cloud scavenging in dissolved and particulate mercury in precipitation - Zixuan Wang; Tao Li; Hongming Cai; Mei Meng; Jiubin Chen; Lin Du; Jiebo Zhen; Ping Du; Yan Wang (Atmospheric Environment, 2026)

“Precursors-in-action” nanoreactor: Coordination-activated self-assembly of cu/Fe bimetallic multifunctional metalloenzyme mimics for cascade-amplified breast cancer therapy - Peng Wang; Xin-Yi Zhang; Ying-Ying Han; Zhi-Yuan Li; Qing-Hua Shen; Long-Bo Yu; Cai-Ping Tan (Chemical Engineering Journal, 2026)

From serpentinization to carbonation: Petrological and geochemical constraints from an ophiolitic reaction profile - Hong-Da Zheng; Qing Xiong; Xiang Zhou; Biao Chang; Hong-Kun Dai; Hong-Zhu Cai; Li Wang; Yi-Cong Li; Long-Fei Xue; Ming Chen; Jian-Ping Zheng (Chemical Geology, 2026)

Long non-coding RNAs in exercise: the hidden regulators of adaptation - Qin Zhang; Zhouren Zhang; Cai Ren; Ping Xiang; Xinhua Li; Ru Ren; Lianting Feng; Jicheng Chen (Pflügers Archiv - European Journal of Physiology, 2026)

Enhancement of anammox coupled arsenate reduction by coexisting iron-bearing minerals - Wentao Wang; Weiyi Xiong; Qing Jiang; Long-jun Ding; Ping Wang; Jiang-Shan Li; Hui Yin; Peng Cai (Journal of Hazardous Materials, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

Research on tunnel construction quality control based on blockchain technology and Bayesian networks - Li-ping Cai; Qiaona Gong; Feng Jiang; Mingzhan Yuan; Zhiyong Xiao; Shuai Zhang; Chengcheng Zheng; Yue Wu (Applied Geophysics, 2026)

Two new monoterpene glycosides from the endophytic fungus Diaporthe nobilis and their cytotoxic effects - Ying Chen; Jian Wang; Cai-Lin Zhao; Xiu-Feng Yang; Jin Ye; Lin-Ping Zhang; Yun-Xiao Li; Fan-Wei Liu; Le Zhang; Bo Song (Natural Product Research, 2026)

Pancancer pro-angiogenic atlas unravels tumor-educated pericyte-augmented anti-angiogenic resistance - Yongqiang Zheng; Hui Sun; Zhe Fu; Haojie Chen; Guangyao Cai; Xin Huang; Yi-Qian Pan; Kai Yu; Ping Chen; Zhuoran Liang; Junteng Li; Jiamin Hu; et al. (Science Bulletin, 2026)

Independent and joint effects of ambient temperature and relative humidity on fetal distress: effect modification by air pollutants - Hua Xiao; Yi Wang; Zongli Qi; Ziwei Ye; Liping Li; Li Mao; Peng Hu; Yuefei Li; Haoyun Zhang; Yao Cheng; Hao Wang; Ping Chen; et al. (International Journal of Biometeorology, 2026)

Effects of dietary Portulaca oleracea L. aqueous extract on growth performance, intestinal health and intestinal microflora of common carp (Cyprinus carpio) - Jing-Tong Huang; Cong-Fu Liu; Yu-Shi Cai; Li-Fang Li; Hai-Tao Zhao; Yan-Ping Yang; Rui-Fang Wang (Animal Feed Science and Technology, 2026)

Facile preparation of new bidentate quaternary ammonium-type stationary phase for the separation of versatile analytes in hydrophilic interaction liquid chromatography - Xiao-dong Cheng; Kai-feng Tan; Cai-yong Lin; Yun-ping Li; Xue-xin Dai (Analytica Chimica Acta, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Experimental study on the wave mitigation characteristics of a grid-type flexible-membrane breakwater under regular waves - Chuan-Rui Li; Jing-Ping Wu; Ming-Liang Cai; Jun-Ao Kang; Chang-Zhe Chen; Hong Fan; Chen-Xia Liu; Shi-Yu Yang; Zi-Wen Xu (Ocean Engineering, 2026)

Deep carbon recycling via the Tianshan basalt province and its contribution to Cenozoic elevated atmospheric CO2 concentration - Xiangsong Wang; Jinlong Yao; Guochun Zhao; Peter A. Cawood; Min Sun; Keda Cai; Xiao-Ping Xia; Pengfei Li; Xijun Liu; Ming Li; Yunying Zhang; Kai Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

Green derivative synchronous fluorescence spectroscopy approach for rapid quantification of Rhodamine B in food samples - Hong-Jun Liu; Jia-Rong He; Yi-Han Guo; Jia-Lin Li; Wei-Peng Cai; Ping-Ping Wu; Yao-Qun Li (Food Control, 2026)

Corrigendum to “Hellebrigenin induces cell cycle arrest and apoptosis in human hepatocellular carcinoma HepG2 cells through inhibition of Akt” [Chemico. Biol. Interact. 219 (2014) 184-194] - Li-Juan Deng; Li-Ping Hu; Qun-Long Peng; Xiao-Lin Yang; Liang-Liang Bai; Anita Yiu; Yong Li; Hai-Yan Tian; Wen-Cai Ye; Dong-Mei Zhang (Chemico-Biological Interactions, 2026)

Characterization of a new diterpenoid glycoside and chemotaxonomical significance of secondary metabolites from Excoecaria acerifolia - Na-Li Song; Jia-Peng Wang; Li-Ping Yang; Sheng-Qi Zhang; Xia Zhao; Le Cai; Zhong-Tao Ding (Biochemical Systematics and Ecology, 2026)

Competition partially decouples the climate-growth relationship in plantations and reduces their drought resilience - Chongfan Guan; Jinsong Zhang; Shoujia Sun; Wanting Gao; Zijing Li; Jinfeng Cai; Ping Meng (Agricultural and Forest Meteorology, 2026)

Robust Noise Identification and Data Reconstruction for Marine Magnetotelluric Time-Domain Data using STA/LTA and Compressive Sensing with Orthogonal Matching Pursuit - Yun-sheng Zhao; Ming-zhen Zhang; Min-gui Cai; Yan Gao; Zhan-xiang He; Jian-ping Li (Applied Geophysics, 2026)

Ecological lock-in and functional mismatch in abandoned coastal ponds: mechanisms and management implications - Yi'na Li; Yanzi Cai; Junjun Bai; Ying Man; Dongxue Li; Qing Wang; Yujia Zhai; Ping Qi; Tian Xie; Baoshan Cui (Journal of Environmental Management, 2026)

Study on spatiotemporal evolution characteristics of temperature field, fracture propagation and oxygen transport in coalfield fire - Fan Tao; Li-Feng Ren; Cai-Ping Wang; Ze-Yang Song; Xin Li; Jin-Rui Wang; Yi-Zhuo Jia; Jun Deng (Fuel, 2026)

Selenylation enhances anti-melanogenic activity of polysaccharide from Cinnamomum cassia Presl. by regulating the CREB/MITF/tyrosinase pathway - Qi-Cong Chen; Ya-Li Wang; Yu Luo; Yan-Ling Zhang; Wen-Xin Li; Wei-Feng Cai; Qian Ni; Cui-Ping Jiang; Qiang Liu; Chun-Yan Shen (Food Research International, 2026)

Investigation of post-rainfall dynamic behavior of anti-dip layered rock slope through shaking table tests - Ping Hu; DeGou Cai; XianQing Xu; HongYe Yan; JunKai Yao; TaiFeng Li (Bulletin of Earthquake Engineering, 2026)

Editor's Note to “Wastewater inputs reduce the CO2 uptake by coastal oceans” [Sci. Total Environ., 901 (2023), 165700] - Yunxiao Li; Liang Xue; Xufeng Yang; Ming Xue; Ping Han; Xiangyu Liu; Han Zang; Pengjin Yang; Wei-Jun Cai; Longjun Zhang (Science of The Total Environment, 2026)

Designing interfacial-engineered S-scheme heterostructures with dual-metal sulfides for efficient solar-to-hydrogen conversion - Xiaofeng Liu; Sihai Cai; Tongyan Ren; Chunrong Li; Geng Tang; Ping He (Fuel, 2026)

Dynamic response of a gentle near-fault bedrock-overburden slope after rainfall based on shaking table tests - Ping Hu; DeGou Cai; Hao Wen; HongYe Yan; JunKai Yao; TaiFeng Li (Bulletin of Engineering Geology and the Environment, 2026)

An Integrated U-Net and Markov Random Field Approach for Pavement Crack Segmentation - Shi-cai Yuan; Ding-zhi Liu; Wei-ping Shi; Pan Li; Yong-qiang Li; Yong Yi (Applied Geophysics, 2026)

Research on spontaneous combustion thermal generation and transfer effects of coal–based activated carbon and its precursors - Hui-Fei Lyu; Fu-Xing Shen; Yue Li; Cai-Ping Wang; Jun Deng; Wei-Feng Wang (Process Safety and Environmental Protection, 2026)

Diapause termination alters the m6A methylation profiles and regulates gene expression associated with early embryonic development in the silkworm (Bombyx mori) - Zhi-Hao Huang; Jia-Yue Yang; Cai-Ping Hou; Shi-Huo Liu; Bing Li; Jie Wang; Shou-jun Huang; Jia-Ping Xu (Journal of Insect Physiology, 2026)

Photothermal mediated bionanocomposite films with pasteurization-like activity for tangerine preservation - Linpin Luo; Wengang Cai; Zihan Qiu; Wenqiao Su; Yiya Ping; Bingzhi Li; Qianjin Liu; Jianlong Wang (Food Chemistry, 2026)

Oligosaccharide mapping analysis through UPLC-Orbitrap-HRMS and enzymatic hydrolysis from Polygonatum odoratum (Mill.) Druce - Qing-Hua Liu; Liu Yang; Yue Wang; Hao-Ming Xiong; Cai-Yun Wang; Guo-Yuan Zhu; Li-ping Bai; Zhi-Hong Jiang; Wei Zhang (Carbohydrate Polymers, 2026)

The emerging role of fatty acids as key bioactive components of Ganoderma lucidum spore oil in alleviating tumor progression - Qi-Jun Chen; Zi-Xuan Li; Guo-Cai Wang; Ting Xie; Guan-Di Xiao; Hui Xu; Jing Li; Xiang Luo; Yi-Fang Li; Lei Liang; Ju-Yan Liu; Yan-Ping Wu; et al. (Journal of Natural Medicines, 2026)

Anthropogenic disturbances drive stepwise geomorphic changes of shoal-channel systems in a tide-dominated estuary - Ping Zhang; Linxi Fu; Xiangyuan Li; Jianliang Lin; Huayang Cai; Zhijun Dai; Qingshu Yang (Marine Geology, 2026)

Structure-optimized hollow carbon spheres from lignite for advanced lithium–sulfur batteries - Yao Huang; Long-Jun Zhang; Wei Wang; Zhan-Ku Li; Xu Liu; Hong-Lei Yan; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui; et al. (Fuel, 2026)

Simultaneous activation of pyroptosis and cGAS-STING pathway with iridium(III) thiophene complexes for enhanced oral squamous cell carcinoma sono-immunotherapy - Jia-Wen Chen; Peng Wang; Jia-Ying Zhou; Yi-Fei Luo; Yi-Ling Li; Jia-Yin Wu; Ling-Ran Li; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Defect passivation with Pb for high-performance Sb2S3 solar cells via vapor transport deposition - Gan Huang; Xin-Yi Cai; Hu Li; Jin-Rui Cai; Ying-Sen Xia; Zhi-Ping Huang; Li-Mei Lin; Fu-Bao Gong; Shui-Yuan Chen; Gui-Lin Chen (Chemical Engineering Journal, 2026)

FeC particle electrodes derived from copper slag boost peroxymonosulfate activation for efficient antibiotic degradation: non-radical pathways mediated by 3d orbital electron reconstruction - Linjin Li; Yaoze Wang; Guangfei Qu; Rui Xu; Yingying Cai; Minhua Cheng; Nanqi Ren; Ping Lu; Minjie He; Jun Wang (Bioresource Technology, 2026)

A new isoprenyl-phenol-type meroterpenoid from mangrove endophytic fungus Aspergillus sp. GXNU-Y65 - Fan-Fan Wang; Guo-Bao Huang; Cai-Hong Lu; Li-Jun Chen; Hui-Zhen Chen; Meng-Qin Luo; Ping-Fang Tao; Ming-Xiong Tan; Feng Qin (Natural Product Research, 2026)

Fate analysis of heavy metals and hydrophobic organic pollutants in tidal flow wetlands: Insights for pollution-specific ecological remediation strategies - Yang Yu; Juan-Ying Li; Si-Xiu Long; Yan-Hong Cai; Bang-Ping Deng; Chun-Yi Zhong; Qian Wang (Marine Environmental Research, 2026)

Plantation type regulates molecular characteristics and chlorine reactivity of soil-derived DOM: Enhanced DBPs formation in legume plantations - Xin-Yi Jiao; Su-Ping Liu; Cai-Shan Wang; Ying-Zhi Ding; Shuang Peng; Zi-Hao Wu; Yan-Chao Jin; Peng Liu; Ding Pan; Xue-Rong Wang; Dong-Bin Wei; Xin-Hui Liu; et al. (Journal of Hazardous Materials, 2026)

Partial consistency of net primary productivity and water-carbon use efficiency in response to climate change among three plantations - Chongfan Guan; ShouJia Sun; Jinsong Zhang; Xiaochuang Hu; Zijing Li; Jinfeng Cai; Ping Meng (Ecological Modelling, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

A metal-immuno photosensitizer strategy: Iridium(III)-zidovudine conjugate triggering sequential organelle stress and synergizing with PD-L1 inhibitor in oral squamous cell carcinoma - Yi-Ling Li; Peng Wang; Wu-Ya Zhang; Rui Zhou; Jia-Ying Zhou; Jia-Wen Chen; Jia-Yin Wu; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Deciphering mechanisms of stress-induced metabolic shifts in Corynebacterium glutamicum by transcriptomics and contextualised modelling - Xiaomeng Ni; Ning Gao; Wenjing Hu; Xuan Guo; Jiao Liu; Jiuzhou Chen; Ningyun Cai; Xiaojia Zhao; Jibin Sun; Yu Li; Yan Zhu; Ping Zheng (Bioresource Technology, 2026)

Association between low daily average temperature and epilepsy outpatient visits: a hospital-based study in Chongqing, China - Pei Jiang; Jing Yang; Yumeng Zhou; Jinchi Gu; Fengxia Liu; Chunlei Tan; Yao Cheng; Hao Wang; Li Mao; Peng Hu; Ping Chen; Ding Liu; et al. (International Journal of Biometeorology, 2026)

Susceptibility of five thrips pests to spinetoram and the frequency of G275E target-site mutation in a major vegetable production region of China - Hong-Ping Tian; Hong-Xia Tian; Jin-Cui Chen; Fu-Jun Li; Jing-Jing Kang; Hui-Juan Li; Jin-Peng Gao; Guo-Cai Lu; Ya-Jun Gong; Shu-Jun Wei (Crop Protection, 2025)

Plantation forest stand age affects the characteristics and the chlorine reactivity of soil-derived dissolved organic matter - Xin-Yi Jiao; Su-Ping Liu; Shuang Peng; Zi-Hao Wu; Fu-Qiang Fan; Le Fang; Yan-Chao Jin; Peng Liu; Cai-Shan Wang; Ding Pan; Xue-Rong Wang; Ying-Zhi Ding; et al. (Water Research, 2025)

Ni/Al-based additives for deep desulfurization of high-sulfur coal: Cooperative desulfurization and sulfur migration behavior - Zheng-Zhi Zhang; Zhan-Ku Li; Jing-Tao Yao; Mu-Xin Liu; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Cai Wang; Zhi-Ping Lei; Shi-Biao Ren; Heng-Fu Shui (Journal of Environmental Chemical Engineering, 2025)

Identifying conservation gaps and proposing climate-smart strategies for amphibians and reptiles on the Qinghai-Tibet Plateau - Lu-Lu Sui; Zhong-Yi Yao; Shun Ma; Sheng-Chao Shi; Xiu-Dong Shi; Li-Wen Liang; Song Tan; Jie Wang; Bo Cai; Feng Xie; Jing-Feng Chen; Bin Wang; et al. (Journal of Environmental Management, 2025)

Fabrication of S-scheme NiFe-LDH/Zn2In2S5 heterojunction for boosting photocatalytic hydrogen evolution - Xiaofeng Liu; Sihai Cai; Chunrong Li; Geng Tang; Tongyan Ren; Ping He (Journal of Environmental Chemical Engineering, 2025)

Wheat germ peptides enhance hypoxia tolerance by modulating gut microbiota and reprogramming brain energy metabolism in mice - Jing-yang Cai; Ying-Ying Liu; Meng-Cheng Li; Xin-Xin Guo; Ai-Mei Liao; Yin-Chen Hou; Quan-Ping Liu; Yong-Chao Fan; Long Pan; Ji-Hong Huang (Food Bioscience, 2025)

Genome-wide survey and expression analysis of JAZ genes in watermelon (Citrullus lanatus) - Yan-Ge Li; Jing Zhang; Xiu-Xiu Cai; Le-Ping Fan; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Molecular Biology Reports, 2025)

Araloside A Induces Raf/MEK/ERK-Dependent Autophagy to Mitigate Alzheimer’s and Parkinson’s Pathology in Cellular and C. elegans Models - Xue Chen; Xing-Yue Zhou; Cai Lan; Hai-Jun Fu; Zhi-Chao Li; Meng-Yi Chen; Yong-Ping Wen; Lu Yu; Da-Lian Qin; An-Guo Wu; Jian-Ming Wu; Xiao-Gang Zhou (Molecular Neurobiology, 2025)

Multigenerational toxic effects of Butylparaben and Hexylparaben on Moina macrocopa - Xue Lei Hu; Ming Chen; Jin Lan Peng; He Ping Huang; Sui Jun Cai; Jin Ling Liu; Yun Hui Li; Lu Wang (Ecotoxicology, 2025)

Plasma-activated water: A novel approach to modulating main pectin, hemicellulose and cellulose metabolism in goji berry cell walls - Kai-Ping Cong; Ting-Ting Li; Cai-E. Wu; Gong-Jian Fan; Dan-Dan Zhou; Xiao-Jing Li; An-Di Suo (Postharvest Biology and Technology, 2025)

Modification of oceanic lithospheric mantle by percolated melts sourced from recycled ancient crust: Evidence from Ca Os isotopes of refractory harzburgites - Hui-Chao Rui; Olivier Namur; Dong-Yang Lian; Peng-Jie Cai; Jie Li; Yurisley Valdes-Mariño; Jing-Sui Yang; Hong-Ping He (Chemical Geology, 2025)

Integrating methane conversion with multi-pathway nitrogen removal for wastewater in membrane-enabled stratified biofilm: System development and microbial dynamics - Chun-Yan Yuan; Yu-Xia; Jia-Hao Huo; Cai-Long Nie; Ke-Xin Zhang; Liang-Feng; Xiao-Li Su; Zi Song; Gen-Ping Yi; Fei-Yun Sun (Bioresource Technology, 2025)

Synthesis and antitumor evaluation of oleanolic acid acylhydrazone derivatives - Juan Cai; Bo-Wen Pan; Liang-Liang Zheng; You-Ping Tian; Zhang-Chao Dong; Li-Juan Liu; Ting-Ting Feng; Ying Zhou; Xiong-Wei Liu; Yang Shi (Molecular Diversity, 2025)

Highly efficient and selective uranium capture across wide concentration and pH ranges by graphitic carbon nitride with multiple Lewis base sites - Wenxiu Sun; Minjie Wang; Qinyan Zhang; Ping Cao; Qingyun Yang; Mi Li; Tao Cai; Qingyi Zeng (Journal of Environmental Chemical Engineering, 2025)

Tailoring molecular structure of coal tar for monolithic phenolic aerogels to reduce enthalpy for solar desalination - Yu Han; Hong-Lei Yan; Zhan-Ku Li; Wei-Dong Zhang; Jing-Chong Yan; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui; Lun-Jing Yan (Journal of Environmental Chemical Engineering, 2025)

Rational design of CdS/Ce-UiO-66 heterostructure for high-efficiency photocatalytic oxidation of amines to imines - Huan Zhang; Cai-Yong Zhu; Wen-Qi Jin; Zi-Yu Li; Peng Li; Wei Gao; Ping Zhang; Xiu-Mei Zhang (Journal of Environmental Chemical Engineering, 2025)

Bimetallic cobalt-cerium loaded copper foam for enhanced paraxylene low-temperature catalytic oxidation: Mechanistic insights and role of oxygen vacancies - Chenyang Zhao; Huanhuan Wu; Guangfei Qu; Yongheng Yuan; Zheng Yuan; Guojun Liu; Zhishuncheng Li; Junyan Li; Yingying Cai; Ping Ning (Journal of Environmental Chemical Engineering, 2025)

The dielectric permittivity modulation effect of phase engineering on SiC whiskers modified reduced graphene oxide composites - Yun-Tian Chen; Bo Cai; Chen-Ming Liang; Shu-Hao Yang; Pei-Yan Zhao; Wen-Ping Li; Guang-Sheng Wang (Chemical Engineering Journal, 2025)

FOXM1 upregulation, promotes immune escape in gastric cancer through activation of Notch signaling pathway - Shangkun Du; Ping Li; Yabin Liu; Bindan Cai; Gang Li; Wenbin Wang; Rui Yan; Xiangkui Zheng; Tianliang Bai (Molecular and Cellular Biochemistry, 2025)

Association Between Whole Blood Iron and Nonalcoholic Fatty Liver Disease in Elderly: A Case–Control Study - Zhe-Ying Jiang; Wei-Jia Meng; Ying Wang; Hua-Qin Su; Bi-Xiu Mao; Cai-Li Wang; Feng-Lian Peng; Cui-Ping Li; Lian-Ping He (Biological Trace Element Research, 2025)

Interfacial electron accumulation of Ir-Co3O4 toward efficient acidic oxygen evolution reaction - Aiying Song; Chao Cai; Ming Jiang; Pengcheng Li; Ping Liao; Yue Huang; Lang Chen; Xuming Yang; Yuanmin Zhu (Chemical Engineering Journal, 2025)

Sulfide-based autotrophic denitrification process with efficient nitrogen removal under high salinity stress: Threshold behaviors and recovery enhanced via glutamate supplementation - Kaiyu Zhang; Qaisar Mahmood; Jiayi Lv; Na Liang; Xiaopeng Zhu; Jinye Li; Jing Cai; Ping Zheng (Bioresource Technology, 2025)

Effect of fulvic acid on aggregate characteristics and humus composition in saline-alkali soil - Rui Cai; Yaru Guo; Yanjie Li; Ling Li; Susu Xu; Ping Gong; Pengfei Li; Hongguang Liu (Plant and Soil, 2025)

BarleyOmics: A comprehensive multi-omics database of barley - Junheng Zhao; Shanggeng Xie; Chenyang Zhang; Zengjie Hu; Xiangqian Lu; Nannan Zheng; Yujie Fu; Jie Yao; Ping Zhou; Danyin Huang; Zhizhong Zhang; Mengdi Li; et al. (Molecular Plant, 2025)

Effect of wave height on seismic fragility of subsea tunnels in sandy seabed - Ling-Yu Xu; Ju-Ping Xi; Jia-Wei Jiang; Fei Cai; Yong-Yi Li; Guo-Xing Chen (Ocean Engineering, 2025)

Investigating the fine structures of ginkgo starch during kernel development and their correlations with thermal properties - Yan Lu; Lian Zhou; Cai-Yun Zhang; Yan Qi; Xiao-Min Zhang; Zhang Pan; Hong-Jia Zhang; Yu-Ping Ling; Qing Liu; Chang-Quan Zhang; Li Wang (Food Chemistry, 2025)

Key aspects of karst development and tunnel construction countermeasures: a case study of the Ehan expressway - Fangtao Li; Zhiping Hu; Yonghui Zhang; Xuexu An; Huaming Li; Lejun Cai; Ping Huang (Bulletin of Engineering Geology and the Environment, 2025)

Understanding citrus aroma: Changes induced by postharvest treatments of fresh fruit - Shuxun Liu; Yuling Cai; Ying Lou; Yan Zhao; Mingfeng Cao; Ping Li; Qing Gu (Postharvest Biology and Technology, 2025)

Metabolomics-based discrimination of geographical variability in quality and antioxidant activity of golden mushroom (Floccularia luteovirens) from the Qinghai-Tibet Plateau - Yishui Cai; Ping Deng; Jiale Liu; Yang Luo; Tajie Sangzhu; Haozheng Li; Yunqi Zhao; Cailin Tang; Manjun Yang (Food Bioscience, 2025)

Insights into mantle metasomatism during oceanic subduction from late Paleozoic (∼260 Ma) high-Mg diorites in the northeastern Tibetan Plateau - Feng-Hui Zou; Jian-Ping Zheng; Cai-Lai Wu; Chang-Qian Ma; Li-Huan Deng (Chemical Geology, 2025)

Enhanced activation of peroxymonosulfate by nickel sulfide with sulfur vacancies for ultrafast organic pollutants degradation: Roles of active sites and mechanism - Cai-Wu Luo; Liang Jiang; Xian-Feng Li; Qiang-Mao Wan; Tian-Jiao Jiang; Sen-Ping Mao; Jing-Qian Guo; Run-Ze Zhao; Chao Xie (Environmental Pollution, 2025)

PdRh bimetallic-loaded α-Fe2O3 nanospindles with Ppb-limit of 3-hydroxy-2-butanone biomarker detection: Particle dimension regulation and oxygen spillover effect - Xing-Yu Wang; Ping-Ping Liu; Hai-Jie Cai; Miao-Miao Li; Chun-Hui Deng; Yong Zhao; Zhao-Huan Zhang; Yong-Heng Zhu (Chemical Engineering Journal, 2025)

Multifunctional Sr/Zn-doped TiO2 micro/nanoporous coating enhances osseointegration by modulating signaling crosstalk of bone-related cells - Tian-Xia Zheng; Nuo-Ya Yang; Jiu-Peng Deng; Wei Dong; Li-Fang Feng; Yuanyuan-Ding; Jin-Ping Yang; Xin-Jia Cai; Yan Liu; Meng-Chun Qi (Chemical Engineering Journal, 2025)

Penicipyrrolidines A−N, pyrrolidine derivatives with inhibitory effects on EMT and fibroblast activation from the mangrove-derived fungus Penicillium sp. DM27 - Li-Ming He; Xuan Deng; Li-Hua Ni; Shi-Qi Cai; Jinhu Chen; Zejin Liao; Mengke Zhang; Hua Shui; Kong-Kai Zhu; Song Wu; Ping Gao; Ariel M. Sarotti; et al. (Marine Life Science & Technology, 2025)

Urinary metabolic alterations associated with occupational exposure to metals and polycyclic aromatic hydrocarbons based on non-target metabolomics - Ping Lu; Rujian He; Yingjun Wu; Bizhi Wu; Hailing Li; Chang He; Meiqing Lin; Mengmeng Wang; Wenwen Cai; Xiantao Shen; Guiying Li; Zhiguo Cao; et al. (Journal of Hazardous Materials, 2025)

The Role of ICP Monitoring in Minimally Invasive Surgery for the Management of Intracerebral Hemorrhage - Ge Zhang; Yunjie Li; Danyang Chen; Zhuojin Wu; Chao Pan; Ping Zhang; Xingwei Zhao; Bo Tao; Han Ding; Cai Meng; Diansheng Chen; Wenjie Liu; et al. (Translational Stroke Research, 2025)
Intracerebral hemorrhage (ICH) is the second major stroke type, with high incidence, high disability rate, and high mortality. At present, there is no effective and reliable treatment for ICH. As a result, most patients have a poor prognosis. Minimally invasive surgery (MIS) is the fastest treatment method to remove hematoma, which is characterized by less trauma and easy operation. Some studies have confirmed the safety of MIS, but there are still no reports showing that it can significantly improve the functional outcome of ICH patients. Intracranial pressure (ICP) monitoring is considered to be an important part of successful treatment in traumatic brain diseases. By monitoring ICP in real time, keeping stable ICP could help patients with craniocerebral injury get a good prognosis. In the course of MIS treatment of ICH patients, keeping ICP stable may also promote patient recovery. In this review, we will take ICP monitoring as the starting point for an in-depth discussion.

Effects of mowing frequency on the interspecific water relationships of a walnut (Juglans regia L.)-alfalfa (Medicago sativa L.) intercropping system - Yao Wang; Chunxia He; Ping Meng; Shoujia Sun; Jinsong Zhang; Pan Xue; Jianxia Li; Jinfeng Cai (Plant and Soil, 2025)

The dynamic behavior of marine soft soil under cyclic wave loading - Chun Li; Ping Yang; Zhaoxue Wu; Wei Chen; Yi Cai (Bulletin of Engineering Geology and the Environment, 2025)

Exploring the physical disruptions of anammox granular sludge under propylene glycol stress: Implications for nitrogen removal and long-term stability - Hui-Min Fu; Xiao-Wen Jiang; Cai-Ping Sun; Shi-Jun Li; Xun Weng; Meng-Wen Peng; Peng Yan; Xiao-Wei Xu; You-Peng Chen; Yu Shen (Journal of Water Process Engineering, 2025)

Experimental investigation on ammonia‑nitrogen adsorption performance of ZSM-5 molecular sieve prepared from coal gangue and fly ash - Qing-Wei Li; Ye-Rui Zhu; Li-Feng Ren; Wen-Ting Xu; Yu-Xin Miao; Yang Xiao; Cai-Ping Wang (Journal of Water Process Engineering, 2025)

Environmental factors ultraviolet a and ozone exacerbate the repeated inhalation toxicity of 6PPD in mice via accelerating the aging reaction - Xianjie Li; Caixia Wu; Ping Yang; Yanxi Li; Shuai Wang; Dan Cai; Ran Wei; Jinfeng Gao; Xuemei Wen; Jieping Luo; Rui Wang; Xueyuan Bai; et al. (Journal of Hazardous Materials, 2025)

Complete genome analysis of a novel nyamivirus from the leaf beetle Aulacophora lewisii - Meng-Nan Chen; Xin-Yi Cai; Zhuang-Xin Ye; Ke-Hui Feng; Peng-Peng Ren; Chuan-Xi Zhang; Jian-Ping Chen; Jun-Min Li; Qianzhuo Mao (Archives of Virology, 2025)

An OLIF Cage Integrated with a Low-Profile Plate and Cross Screws Could Reduce the Risk of Postoperative Complications Biomechanically - Ping Cai; Chen Xu; Zifan Zhang; Zhongxin Fang; Chao Deng; Gang Chen; Guoyou Wang; Jingchi Li (Annals of Biomedical Engineering, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Relationship between pyrolytic sulfur migration behavior and structural composition of high-sulfur fat coal - Zhan-Ku Li; Zheng-Zhi Zhang; Kai Zhang; Hong-Lei Yan; Jing-Chong Yan; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Shi-Gang Kang; Heng-Fu Shui (Fuel, 2025)

Integrated microbiome and metabolomics analysis of spoilage characteristics of modified atmosphere packaged pork - Xueya Wang; Ping Li; Xingguang Chen; Wei Cui; Shenyu Ni; Huaxing Xu; Yujuan Xu; Kezhou Cai; Hui Zhou; Baocai Xu (Food Research International, 2025)

Identification and characterization of GRAS genes in passion fruit (Passiflora edulis Sims) revealed their roles in development regulation and stress response - Xinkai Cai; Denglin Li; Chaojia Liu; Jiayi Chen; Xiuqing Wei; Sitong Hu; Lin Lu; Shengzhen Chen; Qinglong Yao; Shiyu Xie; Xiaowen Xu; Ruoyu Liu; et al. (Plant Cell Reports, 2025)

Structurally diversified sesquiterpenoids from Chloranthus henryi and their neuroprotective activities on H2O2 damaged PC12 cells - Meng-Li He; Lian-Lian Xu; Yang Liu; Yan-Ping Gao; Yong-Ming Luo; Rong-Cai Yue; Fang-You Chen (Phytochemistry, 2025)

Penicipyrrolizidinones A−C, three pyrrolizidinone alkaloids with unprecedented skeletons from the mangrove-derived fungus Penicillium sp. DM27 - Zhenling Chen; Jing-Jing Zhang; Cheng-Yun Huang; Wei-Chen Chen; Li-Ming He; Qing-Qing Tang; Kong-Kai Zhu; Jing Li; Ping Gao; Meng-Ke Zhang; You-Sheng Cai (Phytochemistry, 2025)

Corrigendum to “Cobalt induces neurodegenerative damages through Pin1 inactivation in mice and human neuroglioma cells” [J Hazard Mater 419 (2021) 126378] - Fuli Zheng; Yuqing Li; Fengshun Zhang; Yi Sun; Chunyan Zheng; Zhousong Luo; Yuan-Liang Wang; Michael Aschner; Hong Zheng; Liqiong Lin; Ping Cai; Wenya Shao; et al. (Journal of Hazardous Materials, 2025)

Responses of microbial communities to the addition of different types of microplastics in agricultural soils - Ke Li; Qihao He; Jian Zhu; Jieying Wang; Chang Sun; Ao Tan; Xiaoqi Zhao; Yuanhao Peng; Chao Huang; Jingju Cai; Ping Wang; Zhiming Liu (Environmental Pollution, 2025)

Innovative application of CaO2 in two-phase anaerobic digestion to enhance methane production from waste activated sludge: Condition optimization and mechanistic insights - Danlei Cai; Dunjie Li; Xiaoxia Chen; Lin Wang; Qian Ping; Yongmei Li (Chemical Engineering Journal, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Ecological risks caused by neonicotinoid pesticides in sediments: A case study of freshwater basins in China - Xiaoxia Chen; Pengchong Wen; Yanan Sun; Ping Ding; Haibo Chen; Hui Li; Xin Li; Limei Cai; Yunjiang Yu; Guocheng Hu (Science of The Total Environment, 2024)

Kopsileuconines A−D: Bisindole alkaloids with cytotoxic activity from Kopsia hainanensis - Ni-Ping Li; Shan-Na Chen; Wei-Fang Su; Fen Liu; Lian-Jing Li; Jian-Guo Song; Min-Jing Cheng; Yi-Yi Li; Run-Qiang Chen; Xue-Ping Lei; Wen-Cai Ye; Lei Wang (Phytochemistry, 2024)

Multi-omics analyses of the mechanism for formation of key aroma-active compounds in blood orange wine fermented by Pichia kudriavzevii - Shuxun Liu; Ying Lou; Yan Zhao; Yuling Cai; Mingfeng Cao; Yixian Li; Ping Li; Qing Gu (Food Research International, 2024)

Exploring the variations in molecular characteristics of dissolved organic matter driven by aquaculture types - Li-Ping Li; Xin-Yi Jiao; Shuang Peng; Dong-Bin Wei; Yan-Chao Jin; Cai-Shan Wang; Ding Pan; Peng Liu; Xue-Rong Wang; Yu-Ping Tang; Dong Ren; Xin-Hui Liu (Water Research, 2024)

Bioaccessibility and bioavailability assessment of cadmium in rice: In vitro simulators with/without gut microbiota and validation through in vivo mouse and human data - Fei-Fei Xu; Ying-Si Chen; Xiu-Qin Lin; Ai-Hua Zhong; Min Zhao; Yue-Qi Li; Zi-Yin Li; Yue-Fei Lai; Jia Song; Jia-Liang Pan; Zhan-Fan Cai; Xu-Xia Liang; et al. (Science of The Total Environment, 2024)

Regime shifts in the thermal dynamics of offshore China due to accelerated global warming - Yajun Wang; Huayang Cai; Yu Yan; Bozhi Wang; Huimin Pan; Ping Zhang; Bo Li; Tongtiegang Zhao (Science of The Total Environment, 2024)

Assessment of Microseismic Events via Moment Tensor Inversion and Stress Evolution to Understand the Rupture of a Hard–Thick Rock Stratum - Jie-Fang Song; Cai-Ping Lu; Arno Zang; Xiu-Feng Zhang; Jian Zhou; Zhao-Wei Zhan; Li-Ming Zhao (Rock Mechanics and Rock Engineering, 2024)

Toxicogenomic assessment of hydroxylated metabolites of PBDEs on cetaceans: An in vitro study - Chengzhang Li; Ziyao Tian; Xinying Li; Yajing Sun; Jiashen Tian; Yuqi Wu; Jingting Cai; Yijie He; Edmond Sanganyado; Ping Li; Bo Liang; Wenhua Liu (Chemosphere, 2024)

Highly stable Ag@Au nanowires micromesh as transparent conductive network for stretchable electrochromic modulator - Ping Zhang; Qing Sui; Zhiqiang Liu; Chengyv Hu; Chunjing Li; Xiaodan Guo; Jinhui Wang; Guofa Cai (Chemical Engineering Journal, 2024)

Mn doping and core-shell engineering of silane-modified Mn-TiO2@SiO2 nanoparticles with drastically reduced photocatalytic activity for transparent UV-shielding hybrid materials - Xiangyu Tian; Xinuo Cai; Zixu Zeng; Yi He; Xijun Xu; Lecheng Lei; Cheng Xu; Xin Xu; Yongfeng Xu; Ping Li; Xingwang Zhang (Chemical Engineering Journal, 2024)

Multifunctional and immunoregulatory microenvironment-responsive hydrogel for whole course management of infected diabetic wounds - Zhenyu Luo; Xiaoxue Fu; Hua Jiang; Weikun Meng; Shue Jin; Yongrui Cai; Ze Du; Ping Song; Anjing Chen; Li Li; Peifang Li; Jiali Chen; et al. (Chemical Engineering Journal, 2024)

Efficient and low-cost Ni-NiO/Al2O3 catalysts with dual-active-sites for selective catalytic conversion of phthalic anhydride to phthalide - Liang-Liang Zhang; Xiao-Min Duan; Kai-Xuan Yang; Yu-Bo Xu; Jia-Ping Lu; Wan-Xi Li; Bo-Qiong Li; Cai-Long Xue; Ya-Jie Liu (Chemical Engineering Journal, 2024)

Microbial Community Structure and Metabolism of Xinjiang Fine-Wool Sheep based on High-Throughput Sequencing Technology - Rui Yao; Fulin Li; Xuyang Dong; Yueren Xu; Ruirui Hu; Limin Wang; Kuojun Cai; Xiaogang Liu; Wei Ni; Ping Zhou; Shengwei Hu (Current Microbiology, 2024)

Levels, sources, and health risk assessment of phthalate acid esters in indoor dust of various microenvironments in university - Jun Pan; Xin Li; Ping Ding; Haojie Luo; Sha Cai; Qing Ge; Liuyi Zhang; Guocheng Hu (Chemosphere, 2024)

Rapid evaluation of the quality of Smilax glabra Roxb. using QADS based on FT-NIR combined with multiple intelligent algorithms - Geng-zhi Zhan; Xin-yue Guo; Zi-chao Qiu; Lu-yao Cai; Qian Hu; Ye Gao; Shu-wan Tang; Cun-yu Li; Yun-feng Zheng; Guo-ping Peng (Food Chemistry, 2024)

Effects of sand substrate removal on the intestinal antioxidant and metabolism in Marsupenaeus japonicus - Kuangcheng Zhao; Shaoting Jia; Junxia Wang; Xueqiong Bian; Shibo Chen; Jitao Li; Ping Liu; Jian Li; Yuefeng Cai; Xianyun Ren (Fish & Shellfish Immunology, 2024)

Fe-reinforced silkworm silk with superstrong mechanical properties for mass production - Qingsong Liu; Xin Wang; Yifan Zhou; Yi Li; Zhangchuan Peng; Zhangchen Tang; Xiangyu Cai; Xinyu Fan; Xin Tang; Xiaoyin Tan; Xiaoqian Xie; Xinning Li; et al. (Chemical Engineering Journal, 2024)

Platelet membrane coated Cu9S8-SNAP for NIR-II photoacoustic imaging guided NO repairing acute kidney injury - Xiaojuan Hu; Danping Wu; Shijie Yao; Gongning Chen; Ping Li; Yang Chen; Wancheng Gong; Weijiao Fan; Xiaoyi Chen; Xiaozhou Mou; Yu Cai; Xianghong Yang (Chemical Engineering Journal, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

The impact of CYP3A4 genetic polymorphism on crizotinib metabolism and drug-drug interactions - Jing Wang; Xiao-yu Xu; Xin-yue Li; Jian-chao Luo; Zhe-yan Zhang; Jing Chen; Jian-ping Cai; Li-kang Zhang; Jian-chang Qian (Toxicology and Applied Pharmacology, 2024)

Effects of different curing concentrations and drying times on the microbial community structure and metabolites of dried Spanish mackerel - Jing Li; Yang Liu; Cai-yan Jiang; Xiao-qing Miao; Xiu-ping Dong; Ming Du; Peng-fei Jiang (Food Chemistry, 2024)

Structural characterization of modified soy protein isolate composite coatings and its application on fresh-cut cantaloupe (Cucumis melo cv. Xiaomi) - Tian Yang; Dan-Dan Zhou; Cai-E Wu; Ting-Ting Li; Gong-Jian Fan; Xiao-Jing Li; Kai-Ping Cong; Zhi-Cheng Yan; Xin Cheng (Food Bioscience, 2024)

Near-infrared-LED photostimulated luminescent nanoprobes based on lanthanide-doped SrS nanocrystals - Wei Lian; Qianqi Yang; Yuhan Liu; Datao Tu; Liangzhi Cai; Xiaoying Shang; Bowen Li; Ping Hu; Wei Zheng; Zhuo Chen; Xueyuan Chen (Chemical Engineering Journal, 2024)

IGFBP2 induces podocyte apoptosis promoted by mitochondrial damage via integrin α5/FAK in diabetic kidney disease - Xiaochen Wang; Yifan Zhang; Kun Chi; Yuwei Ji; Keying Zhang; Ping Li; Zhangning Fu; Xu Wang; Shaoyuan Cui; Wanjun Shen; Guangyan Cai; Xiangmei Chen; et al. (Apoptosis, 2024)

Inhibition of flowering by gibberellins in the woody plant Jatropha curcas is restored by overexpression of JcFT - Ping Huang; Jie Yang; Jiapeng Ke; Li Cai; Yingxiong Hu; Jun Ni; Chaoqiong Li; Zeng-Fu Xu; Mingyong Tang (Plant Science, 2024)

VGluT2 neuron subtypes in the paraventricular thalamic nucleus regulate depression in paraquat-induced Parkinson’s disease - Yu Zhang; Yihua Jiang; Zhen Yu; Yinhan Li; Xinpei Lin; Yali Weng; Zhenkun Guo; Hong Hu; Wenya Shao; Guangxia Yu; Fuli Zheng; Ping Cai; et al. (Journal of Hazardous Materials, 2024)

Pathological variations and immune response in Channa argus infected with pathogenic Nocardia seriolae strain - Tingting Zhou; Ping Cai; Junwei Li; Xueming Dan; Zhongsheng Li (Fish & Shellfish Immunology, 2024)

Microglial exosomes in paraquat-induced Parkinson's disease: Neuroprotection and biomarker clues - Jingwen Wu; Wenya Shao; Xu Liu; Fuli Zheng; Yaping Wang; Ping Cai; Zhenkun Guo; Hong Hu; Guangxia Yu; Jianhui Guo; Linlin Yao; Siying Wu; et al. (Environmental Pollution, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Early Triassic high-K granitoids and enclaves of the Daheba pluton, West Qinling (China): Implications for relative contributions of crust and mantle - Feng-Hui Zou; M. Santosh; Chang-Qian Ma; Cai-Lai Wu; Jian-Ping Zheng; Fa-Bin Pan; Han-Ming Gu; Li-Huan Deng (Journal of Asian Earth Sciences, 2024)

The effect of elevation, latitude, and plant richness on robustness of pollination networks at a global scale - Xiang-Ping Wang; Jeff Ollerton; Kit S. Prendergast; Jin-Chao Cai; Ma-Yin Tong; Miao-Miao Shi; Zhong-Tao Zhao; Shi-Jin Li; Tie-Yao Tu (Arthropod-Plant Interactions, 2024)

The response mechanism of transversal mixing of dissolved oxygen to the evolution of secondary flow at the confluence - Xia Shen; Sheng Li; Huanjie Cai; Kai Wang; Xunian Yuan; Dehong Li; Ping Li (Journal of Hydrology, 2024)

LncRNA NR_030777 promotes mitophagy by targeting CDK1-related mitochondrial fission and ATG12 to attenuate paraquat-induced Parkinson's disease - Nengzhou Chen; Hong Hu; Jianping Tang; Fuli Zheng; Zhenkun Guo; Xinpei Lin; Michael Aschner; Wenya Shao; Guangxia Yu; Ping Cai; Wei-Chun Chou; Siying Wu; et al. (Environmental Pollution, 2024)

Redirecting the electron flow to coordinate oxidation and reduction reactions for efficient photocatalytic H2O2 production - Qichao Chen; Cai Ning; Jiawen Fang; Boyu Ping; Guiyang Li; Lingqiao Kong; Jiayi Chen; ZhengMing Sun; Jinlan Wang; Qiushi Ruan; Xianghong Niu; Li Tao (Chemical Engineering Journal, 2024)

Plasma-activated water regulates water distribution to resist softening of goji berries - Kai-Ping Cong; Cai-E. Wu; Ting-Ting Li; Gong-Jian Fan; Dan-dan Zhou; Xiao-jing Li; An-Di Suo; Xu Li (Postharvest Biology and Technology, 2024)

Electrokinetic bioremediation of trichloroethylene and Cr/As co-contaminated soils with elevated sulfate - Qizheng Cai; Chongwen Shi; Zixuan Cao; Zhengtao Li; He-Ping Zhao; Songhu Yuan (Journal of Hazardous Materials, 2024)

Self-floating, monolithic, and aligned phenolic carbon aerogels from coal tar for solar-driven evaporation - Hong-Lei Yan; Jin-Yuan Cheng; Zhan-Ku Li; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui (Fuel, 2024)

Sex differences in the benefit of tea consumption: A critical summation of the epidemiological evidence - Changhuai He; Pin Ye; Xuecheng Zhang; Yiqing Li; Qingping Li; Ping Lü; Chuanqi Cai; Xun Cai (Food Bioscience, 2024)

Exosome-functionalized heterogeneous nanofibrous scaffolds repair bone defects accompanied by muscle injury - Shue Jin; Zeyu Luo; Yongrui Cai; Jing Wen; Pengyu Lu; Xiaoxue Fu; Ping Mou; Anjin Chen; Weikun Meng; Jidong Li; Zongke Zhou; Weinan Zeng (Chemical Engineering Journal, 2024)

Hydro-meteorological factors and inflowing nutrients drive water quality in an impounded lake of China’s South-to-North Water Diversion Project - You Zhang; Mingyuan Gao; Rongkun Liu; Ping Cai; Junfeng Gao; Kuanyi Li; Yongjiu Cai (Environmental Science and Pollution Research, 2024)

Brunonianines A-C, C20-diterpenoid alkaloids with cyano group from Delphinium brunonianum Royle - Qing Li; Zhi-Wei Wang; Mu-Xuan Wang; Hao-Lin Yu; Lei Chen; Zhuoer Cai; Yu Zhang; Min-Min Gu; Yuan-Ling Shao; Hong-Ping Han; Zhi-Xin Liao (Phytochemistry, 2024)

Unravelling hidden threats of water disinfection: Toxicity evaluation and toxic products identification during diclofenac degradation - Ding Pan; Cheng Zhang; Cai-Shan Wang; Peng Zhang; Xin-Yi Jiao; Qian-Ru Ma; Li-Ting Wang; Dai-Jun Li; Li-Ping Li (Environmental Pollution, 2024)

Iodine Acetonitrile as a Drinking Water Disinfectant Showed a Potential Toxic Effect on Organism - Ya-Ping Li; Jie-Wen Cai; Pin-Ying Su; Shi-Ming Xie; Jia-Xuan Lai; Zi-Ru Xian; Jing-Da Qiao (Water, Air, & Soil Pollution, 2024)

Brittleness ductility transition depth of new fracture in the Baodi Miaozhuang Uplift - He Li; Yi-Bing Dong; Yi-Xi Wang; Wu-Ping Gao; Cheng-Guo Yan; Ling-Ling Cai; Bo-Yang Wu; Peng Zhao (Applied Geophysics, 2024)

Whole genome analysis of intestinal source Bacillus and its effect on the prevention and control of hybrid snakehead (Channa maculata ♀ × Channa argus ♂) nocardiosis - Tingting Zhou; Ping Cai; Junwei Li; Zhongsheng Li; Xueming Dan; Xiande Huang; Xiaoyong Zhang (Frontiers in Marine Science, 2024)
In order to explore the antagonistic mechanism of Lysinibacillus sphaericus AEB18 against Nocardia seriolae , the whole genome of strain AEB18 was sequenced, and the effect of strain AEB18 in controlling nocardiosis of hybrid snakehead was verified in vitro and in vivo . Strain AEB18 genome was a circular DNA of 4,653,716 base pairs (bp) and GC content of 37.4%, predicting 4,529 coding genes, 108 tRNAs, 37 rRNAs, and 95 non-coding (nc)RNAs. The eggNOG (Non-supervised Orthologous Groups), GO (Gene Ontology), KEGG (Kyoto Encyclopedia of Genes and Genomes) and the CAZy (Carbohydrate-Associated Enzyme) database annotated the strain AEB18 genome to 3,965, 3,325, 2,061, and 112 genes, respectively. Furthermore, nine gene clusters, including polyketones, non-ribosomal synthetic peptides, β-lactones, terpenes, ribosomal synthetic peptides, and other secondary metabolites with bacteriostatic effect were obtained through the prediction of secondary metabolites of strain AEB18. After the addition of L. sphaericus AEB18 (1 × 10 9 CFU/g) with a mass fraction of 1% to the basal diet for 21 days, the weight gain rate and the activity of amylase in intestinal chyme of hybrid snakehead were significantly increased ( P < 0.05). In addition, hybrid snakehead fed with L. sphaericus AEB18 supplemented diets showed significantly reduced mortality rate ( P< 0.05) after N. seriolae infection, compared with the control group (mortality rate was 100%). Overall, L. sphaericus AEB18 positively affected hybrid snakeheads, promoted growth and reduced mortality rate of hybrid snakeheads with nocardiosis. Taken together, the L. sphaericus AEB18 possesses great potential as a biocontrol agent, which can be commercially developed to improve disease control in freshwater aquaculture.

Highly efficient activation of periodate by a manganese-modified biochar to rapidly degrade methylene blue - Jiamin Gong; Honghui Jiang; Xiang Li; Hao Cheng; Ziqi Wang; Jingju Cai; Meifang Li; Ping Wang; Hui Wang; Xi Hu; Xinjiang Hu (Environmental Research, 2024)

Rosmarinic acid against cognitive impairment via RACK1/HIF-1α regulated microglial polarization in sepsis-surviving mice - Dan-yang Liu; Yao Wu; Zi-qi Feng; Yang Yu; Hua-wei Cai; Shi-ping Liao; Tao Zeng; Ling Zhu; Xia Wang; Li-hong Wan (Chemico-Biological Interactions, 2024)

Mechanism of Antidepressant Action of (2R,6R)-6-Hydroxynorketamine (HNK) and Its Compounds: Insights from Proteomic Analysis - Chaohui Zhen; Chong Wang; Yanjun Ma; Yuli Pang; Feiyue Cai; Jiali Meng; Yuefei He; Ping Xiao; Jianxi Liu; Xi Mei; Shupeng Li; Guanzheng Wu; et al. (Molecular Neurobiology, 2024)

Gas barrier coating based on cellulose nanocrystals and its preservation effects on mango - Mingxia Li; Zhenxu Shi; Shulin He; Qiang Hu; Ping Cai; Lin Gan; Jin Huang; Yongqiang Zhang (Carbohydrate Polymers, 2023)

Assessment of Cadmium Concentrations in Foodstuffs and Dietary Exposure Risk Across China: A Metadata Analysis - Ying Qing; Yongzhen Li; Xinyi Cai; Wenting He; Shishi Liu; Yunhe Ji; Meng Jiang; Linjing Yang; Jutao Wang; Siyuan Ping; Yu Chen; Yingyi Luo; et al. (Exposure and Health, 2023)
Cadmium (Cd) is a persistent and toxic heavy metal widely present in the environment and can cause damage to a variety of human organs and systems. Based on published studies from 2000 to 2021, this study established a comprehensive database of Cd concentrations in Chinese foods, and described the spatial and temporal trends of Cd concentrations in foods across China. The average Cd concentration in total foodstuff was 0.078 mg/kg, with edible fungi and algae having the highest concentrations, followed by aquatic foods, nuts, cereals, beans, vegetables, meats, eggs, milk, and fruits. The average dietary Cd exposure of Chinese residents was 34.3 μg/day (varying from 22.6 to 54.5 μg/day across regions), with the highest exposures in South China. Cereals (46.2%), vegetables (19.2%), and aquatic food (18.4%) contributed the most to the dietary Cd exposure of Chinese residents. According to Monte Carlo simulations of the risk assessment of dietary exposure to Cd, approximately, 15.4% of the Chinese population exceeded the Joint FAO/WHO Expert Committee on Food Additives health-based guidance value. The hazard quotient and excess lifetime cancer risk indices of dietary Cd exposure indicated that the Chinese residents would not be at significant non-cancer and carcinogenic risk. In summary, this study obtained comprehensive and reliable results on Cd concentrations in Chinese food and dietary Cd exposure risk of Chinese residents, which can provide a data base for the development of dietary Cd exposure limits in China.

Wastewater inputs reduce the CO2 uptake by coastal oceans - Yunxiao Li; Liang Xue; Xufeng Yang; Qinsheng Wei; Ming Xin; Ming Xue; Chenhua Han; Ping Han; Xiangyu Liu; Han Zang; Pengjin Yang; Xiangbin Ran; et al. (Science of The Total Environment, 2023)

Lindenane sesquiterpenoid dimers from Chloranthus holostegius with anti-neuroinflammatory activities in BV-2 microglia - Zhao-Chun Zhan; Yi-Ping Xia; Qing Tang; Hui-Hui Zhu; Jing-Yi Du; Jun-Xing Cai; Yan-Jun Chen; Zhong-Nan Wu; Yao-Lan Li; Neng-Hua Chen; Guo-Cai Wang; Yu-Bo Zhang (Phytochemistry, 2023)

Genetic variations of CYP3A4 on the metabolism of itraconazole in vitro - Sai-li Xie; Xiayan Zhu; Nanyong Gao; Qianmeng Lin; Chaojie Chen; Yun-jun Yang; Jian-ping Cai; Guo-xin Hu; Ren-ai Xu (Food and Chemical Toxicology, 2023)

Alteromonas Aquimaris sp. nov., Isolated from Surface Seawater - Qin Wang; Xin-Yuan Hu; Li-Ping Sun; Hui-Jing Niu; Cai-Xia Pei; Yi Li; Cheng-Qiang Xia (Current Microbiology, 2023)

Arbuscular mycorrhiza changes plant facilitation patterns and increases resource use efficiency in intercropped annual plants - Shuang-Guo Zhu; Hai-Xia Duan; Hong-Yan Tao; Li Zhu; Rui Zhou; Yu-Miao Yang; Xiao-Lin Zhang; Wen-Ying Wang; Hao Zhu; Wei Zhang; Ren-Qing Wang; Xiu-Ping Tao; et al. (Applied Soil Ecology, 2023)

Sedimentary Environment Interpretation and Organic Matter Enrichment of the Lower Cambrian Shuijingtuo Shale in the Yichang Slope, South China: Insight from Sedimentary Geochemical Proxies with Major/Trace Elements - Sile Wei; Mingyi Hu; Sheng He; Wei Yang; Qing He; Quansheng Cai; Ping Li (Journal of Marine Science and Engineering, 2023)
The vertical geochemical variations in total organic carbon (TOC) content and major and trace elements of the Lower Cambrian Shuijingtuo Formation from the Yichang Slope in the Upper Yangtze were investigated to assess the environmental conditions (redox conditions, water mass restriction, terrigenous input, relative sea-level terrestrial, and paleoproductivity) and to determine the primary controlling factors for organic matter enrichment. The Shuijingtuo Shale is divided into three intervals. The lithofacies of interval I are mainly black siliceous shale with high TOC content, and interval II is mainly black siliceous shale with moderate TOC content. Interval III consists of black, clay-rich siliceous shale and dark-gray calcareous shale and is characterized by a low TOC content. The effects of diagenesis and hydrothermal activity on the elements were evaluated prior to analyzing the environmental condition. There are good positive correlations between TOC and U/Al or Mo/Al ratios, suggesting that major/trace elements still retain the geochemical signature of the sedimentary environment. Meanwhile, the geochemical proxies consisting of Al, Fe, Mn, and Ti indicate that the study area did not experience hydrothermal deposits. The redox proxies (U/Th, Corg:Ptot, and MoEF–UEF) indicate that the interval I samples were formed under a strong reducing condition. The diagram of TOC vs. Mo indicates that the water mass was moderately restricted during the deposition of interval I shales. Proxies of terrigenous input and relative sea-level (Zr/Al and Zr/Rb) suggest that the organic-rich shales at the bottom were deposited under a relatively high sea-level and experienced minimal input of terrigenous debris from the source area. Additionally, the paleoproductivity indicated by Sibio and (Ni + Cu + Zn)/Al was high for interval I samples. During the interval II period, the relative sea-level began to decline, the seawater still remained in reducing conditions, and there was no change in the productivity, but the input of terrigenous debris increased significantly. In the interval III depositional period, the relative sea-level continued to decrease, the seawater shifted to a dysoxic condition, and the paleoproductivity was also at a lower level. The evolution of the sedimentary environment indicates that the high TOC content in the interval I samples is mainly attributed to the strong reducing condition, the preservation condition and debris dilution together control the organic matter content within the interval II samples, and the low TOC content within the interval III samples is constrained by a combination of the poor preservation conditions and lower paleoproductivity.

A new sesquiterpenoid from the aconitum -derived fungus Aspergillus fumigatus M1 - Hao Ding; Jia-Peng Wang; Si-Ping Deng; Jun-Li Gan; Bing-Xian Li; Ling-Ling Yao; Sheng-Qi Zhang; Le Cai; Zhong-Tao Ding (Natural Product Research, 2023)

Bi0·5Na0·5TiO3/ZnO Z-scheme heterojunction for piezo-photocatalytic water remediation: Mechanical energy harvesting and energy band configuration - Peng Wang; Wanqian Cai; Fangyuan Yu; Ping Zhou; Mei Lin; Cong Lin; Tengfei Lin; Min Gao; Chunlin Zhao; Xiangqi Li; Xiao Wu (Chemosphere, 2023)

Effects of interspecific interactions on soil carbon emission and efficiency in the semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Shuang-Guo Zhu; Hong-Yan Tao; Aziz Khan; Aimee Grace Uzamurera; Bao-Zhong Wang; Jun-Ming Jin; Yue Ma; Wen-Bo Li; Xiu-Ping Tao; et al. (Soil and Tillage Research, 2023)

Association between urinary neonicotinoid insecticide levels and dyslipidemia risk: A cross-sectional study in Chinese community-dwelling elderly - Jian Sun; Pei He; Rui Wang; Zhong-Yuan Zhang; Yu-Qing Dai; Xiao-Yu Li; Si-Yu Duan; Cai-Ping Liu; Hao Hu; Guang-Jun Wang; Yan-Ping Zhang; Fei Xu; et al. (Journal of Hazardous Materials, 2023)

Persulfate activation with nitrogen and sulfur co-doped porous biochar to remove thiamethoxam: A combination of radicals and nonradicals - Ziqi Wang; Xiangyu Meng; Yewen Yang; Honghui Jiang; Xinyuan Tan; Jingju Cai; Meifang Li; Ke Ouyang; Tingting Li; Ping Wang; Hui Wang; Xinjiang Hu (Journal of Environmental Chemical Engineering, 2023)

Late-Permian subduction-to-collision transition and closure of Paleo-Asian Ocean in eastern Central Asian Orogenic Belt: Evidence from borehole cores in the Songliao Basin, Northeast China - Haihua Zhang; Liang Qiu; Dan-Ping Yan; Zifu Zhao; Keda Cai; Jian Zhang; Shuwang Chen; Yongfei Li; Ying Song; Yuejuan Zheng; Shouliang Sun; Fanhao Gong; et al. (Gondwana Research, 2023)

Leaf senescence, nitrogen remobilization, and productivity of maize in two semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Fei Mo; Aziz Khan; Asfa Batool; Wei Zhang; Jun-Sheng Lu; Ying Zhu; Bao-Zhong Wang; Yu-Miao Yang; Jing Wang; et al. (European Journal of Agronomy, 2023)

Synergization of an endoplasmic reticulum-targeted iridium(III) photosensitizer with PD-L1 inhibitor for oral squamous cell carcinoma immunotherapy - Jia-Ying Zhou; Qing-Hua Shen; Xiao-Jing Hong; Wu-Ya Zhang; Qiao Su; Wu-Guo Li; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2023)

Experimental research progress of grid to rod fretting in pressurized water reactors - Yong-jun Jiao; Zheng-yang Li; Zeng-ping Pu; Mei-yin Zheng; Quan-yao Ren; Zhen-bing Cai; Yin-wei Wu; Sui-zheng Qiu (Annals of Nuclear Energy, 2023)

Functional evaluation of CYP2C19 and CYP3A4 gene polymorphism on ibuprofen metabolism - Ling-Jing Yuan; Xiang-Yu Li; Jin-Huan Ni; Jing Wang; Xiao-Yu Xu; Jian-Chao Luo; Qi Zhou; Guo-Xin Hu; Jian-Ping Cai; Jian-Chang Qian (Toxicology and Applied Pharmacology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Plant facilitation improves carbon production efficiency while reducing nitrogen input in semiarid agroecosystem - Wei Wang; Meng-Ying Li; Shuang-Guo Zhu; Aziz Khan; Xiu-Ping Tao; Guang-Fu Huang; Hai-Ying Liu; Wei Zhang; Hong-Yan Tao; Dong-Shan Gong; Chao Song; You-Cai Xiong (CATENA, 2023)

MLK3 localizes mainly to the cytoplasm and promotes oxidative stress injury via a positive feedback loop - Yu Jiang; Bai-Xue Wang; Yi Xie; Li Meng; Meng Li; Cai-Ping Du (Cell Biochemistry and Biophysics, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

Enzymatic activity of 38 CYP2C9 genotypes on ibuprofen - Ling-jing Yuan; Xiang-yu Li; Feng Ye; Xin-yue Li; Qing-qing Li; Yun-shan Zhong; Shi-yu Wang; Ya-hui Wang; Guo-xin Hu; Jian-ping Cai; Jun-wei Li (Food and Chemical Toxicology, 2023)

Porphyrin-based donor with asymmetric ending groups enables 16.31% efficiency for ternary all-small-molecule organic solar cells - Haojiang Shen; Yixuan Xu; Wentao Zou; Wenqing Zhang; Jianfeng Li; Ping Cai; Yuan Guo; Huajun Xu; Xiaotao Hao; Yanna Sun; Yuanyuan Kan; Yingguo Yang; et al. (Chemical Engineering Journal, 2023)

Effects of drug-drug interactions and CYP3A4 variants on alectinib metabolism - Ya-nan Liu; Jie Chen; Jing Wang; Qingqing Li; Guo-xin Hu; Jian-ping Cai; Guanyang Lin; Ren-ai Xu (Archives of Toxicology, 2023)

The intramolecular integration of carbonyl and N-nitroamino groups to effectively balance the energy and sensitivity of N-nitroamino-functionalized bisazoles - Jinxiong Cai; Jinya Zhang; Jin Xiong; Rui Li; Teng Fei; Qi Lai; Ping Yin; Siping Pang (Chemical Engineering Journal, 2023)

Investigation of heavy metal flows in a copper pyrometallurgical process of a typical smelter - Xiang Li; Xueqian Wang; Bing Cai; Langlang Wang; Li Yuan; Ping Ning (Process Safety and Environmental Protection, 2023)

Tetracycline degradation by persulfate activated with nitrogen magnetic graphene oxide confined Fe/Co dual single-atom catalyst: Performance and degradation mechanism - Chenxi Huang; Meifang Li; Ping Wang; Shiyu Song; Beixia Chai; Meijuan Zhang; Xinjiang Hu; Jingju Cai; Shaohua Wu; Qingyun He (Journal of Environmental Chemical Engineering, 2023)

Doublecortin-Expressing Neurons in Human Cerebral Cortex Layer II and Amygdala from Infancy to 100 Years Old - Ya-Nan Li; Dan-Dan Hu; Xiao-Lu Cai; Yan Wang; Chen Yang; Juan Jiang; Qi-Lei Zhang; Tian Tu; Xiao-Sheng Wang; Hui Wang; Ewen Tu; Xiao-Ping Wang; et al. (Molecular Neurobiology, 2023)

Southern Ocean warming and its climatic impacts - Wenju Cai; Libao Gao; Yiyong Luo; Xichen Li; Xiaotong Zheng; Xuebin Zhang; Xuhua Cheng; Fan Jia; Ariaan Purich; Agus Santoso; Yan Du; David M. Holland; et al. (Science Bulletin, 2023)

Arc bead ignition of a cellulose fuel bed derived from experimental and simulated data - Hui-Fei Lyu; Cai-Ping Wang; Jun Deng; Wei-Feng Wang; Yang Li; Chi-Min Shu (Fuel, 2023)

Uncovering acid resistance genes in lactic acid bacteria and impact of non-viable bacteria on bacterial community during Chinese strong-flavor baijiu fermentation - Xinyue Li; Guangxun Tan; Ping Chen; Kaiyun Cai; Weiwei Dong; Nan Peng; Shumiao Zhao (Food Research International, 2023)

Multi-scale structure characterization of ozone oxidized waxy rice starch - Jing Li; Meng Du; Zia-ud Din; Ping Xu; Lei Chen; Xi Chen; Yuehui Wang; Yang Cao; Kun Zhuang; Jie Cai; Qingyun Lyu; Xianhui Chang; et al. (Carbohydrate Polymers, 2023)

Association between the NEP rs701109 polymorphism and the clinical efficacy and safety of sacubitril/valsartan in Chinese patients with heart failure - Hong-Yu Luo; Li-Chen Gao; Hui-Zhi Long; Zi-Wei Zhou; Shuo-Guo Xu; Feng-Jiao Li; Hong-Li Li; Yan Cheng; Cai-Xia Li; Xing-Yu Peng; Liang Li; Ran Chen; et al. (European Journal of Clinical Pharmacology, 2023)

Undescribed phloroglucinol derivatives with antiviral activities from Dryopteris atrata (Wall. Ex Kunze) Ching - Ji-hui Zhang; Jin-lin Chen; Wei-bin Xu; Yi-ping Xia; Hao-yue Zhu; Jing-hao Wang; Yao-lan Li; Guo-cai Wang; Yu-bo Zhang; Neng-hua Chen (Phytochemistry, 2023)

Preparation and characterization of carboxymethyl chitosan/pullulan composite film incorporated with eugenol and its application in the preservation of chilled meat - Zhen Zeng; Yu-Jing Yang; Qian Tu; Yu-Ying Jian; Da-Ming Xie; Ting Bai; Shan-Shan Li; Yun-Tao Liu; Cheng Li; Cai-Xia Wang; Ai-Ping Liu (Meat Science, 2023)

Water transport in continental subduction zones: Constraints from eclogite from the Dabie orogen, east-central China - Zhi-Min Wang; Ren-Xu Chen; Yong-Fei Zheng; Shuning Li; Lin Zhu; Bing Gong; Xiang-Ping Zha; Wan-Cai Li (Journal of Asian Earth Sciences, 2023)

Eicosane-based thermo-conductive phase change composite for efficient capture solar energy and using in real-environment as power source - Linhong Li; Maohua Li; Yue Qin; Yapeng Chen; Wen Dai; Zhenbang Zhang; Xiangdong Kong; Ping Gong; Yandong Wang; Rongjie Yang; Bo Wang; Tao Cai; et al. (Chemical Engineering Journal, 2023)

Accelerated sulfate radical generation from peroxymonosulfate by ZIF-67-derived Co3O4 encapsulated in g-C3N4: A gift from in situ growth - Jinping Liang; Ling Fu; Kai Gao; Ping Zhang; Xiaoguang Duan; Xiaobo Gong; Li Cai (Chemical Engineering Journal, 2023)

Gas in place and its controlling factors of deep shale of the Wufeng-Longmaxi Formations in the Dingshan area, Sichuan Basin - Ping Gao; Xianming Xiao; Dongfeng Hu; Ruobing Liu; Fei Li; Qin Zhou; Yidong Cai; Tao Yuan; Guangming Meng (Frontiers of Earth Science, 2023)

Micropyrones A and B, two new α -pyrones from the actinomycete Microbacterium sp. GJ312 isolated from Glycyrrhiza uralensis Fisch - Ying-Ting Xu; Yu-Cai Luo; Jing-Hua Xue; Yu-Ping Li; Lei Dong; Wen-Jun Li; Zhong-Yu Zhou; Xiao-Yi Wei (Natural Product Research, 2023)

Temperature-dependent effects of neonicotinoids on the embryonic development of zebrafish (Danio rerio) - Yolina Yu Lin Wang; Yan-Er Cai; Syed Shabi Ul Hassan Kazmi; Jing Yang; Yuwen Wang; Ping Li; Wenhua Liu; Zhen Wang (Frontiers in Marine Science, 2023)
The agricultural use of neonicotinoids is increasing worldwide and poses a threat to non-target organisms. The existing toxicity data of neonicotinoids that is mainly focused on widely used neonicotinoids ignores the influence of environmental factors, like temperature, related to climate changes, etc . To fill this data gap, the present study assessed the temperature-dependent toxicity of six neonicotinoids at four temperatures. Briefly, a fish embryo toxicity test was performed at the following temperatures—20, 23, 28, and 33°C—on zebrafish embryos to evaluate the lethal and sublethal effects of these toxicants. At 28°C, the lethal toxicity (LC 50 ) values for these toxicants were cycloxaprid—3.36 mg/L, nitenpyram—7.08 mg/L, paichongding—17.2 mg/L, imidaclothiz—738.6 mg/L, dinotefuran—2,096 mg/L, and thiamethoxam—4,293 mg/L, respectively. Among the sublethal effects, the enzymatic activities changed significantly in neonicotinoid treatments, which revealed oxidative stress, metabolic disorders, and neurotoxicity. Particularly, acetylcholinesterase inhibition and glutathione S-transferase activation showed a significant dose–response relationship. However, cycloxaprid, nitenpyram, and paichongding were found to be more potent compared with imidaclothiz and thiamethoxam. The influence of temperature on these neonicotinoids demonstrated an inverted V-shaped relationship, in which toxicity decreased with the increase of temperature and then increased with the increase of temperature after exceeding the optimum temperature. This study provides a reference for the multiscale effects and potential mechanisms of neonicotinoids. Temperature-dependent toxicity is of great significance for future toxicity testing and risk assessment of chemicals in the face of global climate changes.

Confined Fe single atomic sites on (100) plane of anatase TiO2 nanofibers boost white LED driven Fenton-like norfloxacin degradation - Zhilin Ji; Rongsheng Cai; Wanneng Ye; Ping Lu; Chung-Li Dong; Yu-Cheng Huang; Xilin She; Denys S. Butenko; Yiming Liu; Yukun Zhu; Dongjiang Yang (Journal of Cleaner Production, 2023)

Ultrasonic-assisted stewing enhances the aroma intensity of chicken broth: A perspective of the aroma-binding behavior of fat - Jun Qi; Chuan-kang Jia; Wen-wen Zhang; Hui-min Yan; Qing-yuan Cai; Xiu-ning Yao; Kuo Xu; Ying Xu; Wen-ping Xu; Guo-yuan Xiong; Mei-qi Li (Food Chemistry, 2023)

Correction to: Ketone Body Rescued Seizure Behavior of LRP1 Deficiency in Drosophila by Modulating Glutamate Transport - Jin-Ming Zhang; Ming-Jie Chen; Jiong-Hui He; Ya-Ping Li; Zhi-Cai Li; Zi-Jing Ye; Yong-Hui Bao; Bing-Jun Huang; Wen-Jie Zhang; Ping Kwan; Yu-Ling Mao; Jing-da Qiao (Journal of Molecular Neuroscience, 2023)

Environmental impact of typical zinc smelting that implements solid waste collaborative utilization in China - Wei-Ning Liu; Yao Shi; Chen-Mu Zhang; Lang-Ming Liu; Hui-Quan Li; Bin Lu; Yuan-Bo Xie; Cai-Bei Zhuang; Tian-You Sun; Wei-Ping Liu; Xue Guan; Ying-Yan Hu (The International Journal of Life Cycle Assessment, 2022)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Energy substrate metabolism and oxidative stress in metabolic cardiomyopathy - Ze Chen; Zhao-Xia Jin; Jingjing Cai; Ruyan Li; Ke-Qiong Deng; Yan-Xiao Ji; Fang Lei; Huo-Ping Li; Zhibing Lu; Hongliang Li (Journal of Molecular Medicine, 2022)

Salinimicrobium sediminilitoris sp. nov., Isolated from a Tidal Flat - Cheng-Qiang Xia; Hui-Jing Niu; Kai-Shi Dong; Li Guan; Li-Ping Sun; Qin Wang; Yan-Jiao Zhang; Yi Li; Cai-Xia Pei (Current Microbiology, 2022)

Effect of posaconazole on the concentration of intravenous and oral cyclosporine in patients undergoing hematopoietic stem cell transplantation - Li-E Zhu; Hui-Ping Huang; Yi-Peng Cai; Yan Wang; Bao-Hua Xu; Mao-Bai Liu; Xue-Mei Wu (European Journal of Clinical Pharmacology, 2022)

Ketone Body Rescued Seizure Behavior of LRP1 Deficiency in Drosophila by Modulating Glutamate Transport - Jin-Ming Zhang; Ming-Jie Chen; Jiong-Hui He; Ya-Ping Li; Zhi-Cai Li; Zi-Jing Ye; Yong-Hui Bao; Bing-Jun Huang; Wen-Jie Zhang; Ping Kwan; Yu-Ling Mao; Jing-da Qiao (Journal of Molecular Neuroscience, 2022)

Sandstorms cause shrinkage of Haloxylon ammodendron shrubs and limit their self-renewal - Sheng-bo Shi; Dang-wei Zhou; Fang-lin Wang; Rui Shi; Tao Sun; Tian-cai Li; Jia-lin Ma; Xiang Wan; Jian-ping Ma; Jing-nian Tang (Theoretical and Experimental Plant Physiology, 2022)
Haloxylon ammodendron is an excellent windproof and sand-fixing species whose shrubs are widely cultivated in arid desert areas of northwest China but are now at risk of degradation and shrinkage. Using the chlorophyll fluorescence image analysis technique, the response of photosystem II (PSII) photochemical efficiency and non-photochemical quenching capacity to sediment-carrying wind and sand-free wind (both 12 m s −1 ) lasting for 10, 20, and 40 min were studied with seedlings in a wind tunnel. The results indicated that the sand-free wind had little influence on the maximum quantum efficiency of PSII photochemistry, F v / F m , which was approximately 0.80 on average; however, the F v / F m decreased over exposure time in the sediment-carrying wind group, with values smaller than those in the wind-only group. The non-photochemical quenching was sensitive to wind erosion, and sediment-carrying wind could aggravate the reduction in non-photochemical quenching ( NPQ ). Except for the 10 min duration, the maximum quantum efficiency of PSII photochemistry after dark recovery for 15 min, F v r / F m r , was lower in seedlings exposed to sediment-carrying wind than in those in the wind-only group. Compared to wind-only, wind-blown sand led to a water imbalance and withering in seedlings, causing the concentration of photosynthetic pigments (when based on the fresh mass of green branches) to not decrease. With a longer exposure time to sediment-carrying wind, both the probability and extent of lignified spots occurring increased in green assimilative branches. Our results demonstrated that sediment-carrying wind at 12 m s −1 lasting for 20 min or more could cause irreversible damage to the photosynthetic apparatus of H. ammodendron seedlings. Therefore, frequent and strong sandstorms are the main disturbance factors leading to shrinkage of shrubs and limiting their self-renewal.

Size distributions and dry deposition fluxes of water-soluble inorganic nitrogen in atmospheric aerosols in Xiamen Bay, China - Shui-Ping Wu; Xiang Li; Yang Gao; Mei-Jun Cai; Chao Xu; James J. Schwab; Chung-Shin Yuan (Journal of Atmospheric Chemistry, 2022)

MoOpy2 is essential for fungal development, pathogenicity, and autophagy in Magnaporthe oryzae - Ying‐Ying Cai; Jing‐Yi Wang; Xi‐Yu Wu; Shuang Liang; Xue‐Ming Zhu; Lin Li; Jian‐Ping Lu; Xiao‐Hong Liu; Fu‐Cheng Lin (Environmental Microbiology, 2022)
Summary The development and pathogenicity of the fungus Magnaporthe oryzae , the causal agent of destructive rice blast disease, require it to perceive external environmental signals. Opy2, an overproduction‐induced pheromone‐resistant protein 2, is a crucial protein for sensing external signals in Saccharomyces cerevisiae . However, the biological functions of the homologue of Opy2 in M. oryzae are unclear. In this study, we identified that MoOPY2 is involved in fungal development, pathogenicity, and autophagy in M. oryzae . Deletion of MoOPY2 resulted in pleiotropic defects in hyphal growth, conidiation, germ tube extension, appressorium formation, appressorium turgor generation, and invasive growth, therefore leading to attenuated pathogenicity. Furthermore, MoOpy2 participates in the Osm1 MAPK pathway and the Mps1 MAPK pathway by interacting with the adaptor protein Mst50. The interaction sites of Mst50 and MoOpy2 colocalized with the autophagic marker protein MoAtg8 in the preautophagosomal structure sites (PAS). Notably, the Δ Moopy2 mutant caused cumulative MoAtg8 lipidation and rapid GFP‐MoAtg8 degradation in response to nitrogen starvation, showing that MoOpy2 is involved in the negative regulation of autophagy activity. Taken together, our study revealed that MoOpy2 of M. oryzae plays an essential role in the orchestration of fungal development, appressorium penetration, autophagy and pathogenesis.

Oxidation of organoarsenicals and antimonite by a novel flavin monooxygenase widely present in soil bacteria - Jun Zhang; Jian Chen; Yi‐Fei Wu; Zi‐Ping Wang; Ji‐Guo Qiu; Xiao‐Long Li; Feng Cai; Ke‐Qing Xiao; Xiao‐Xu Sun; Barry P. Rosen; Fang‐Jie Zhao (Environmental Microbiology, 2022)
Summary Arsenic can be biomethylated to form a variety of organic arsenicals differing in toxicity and environmental mobility. Trivalent methylarsenite (MAs(III)) produced in the methylation process is more toxic than inorganic arsenite (As(III)). MAs(III) also serves as a primitive antibiotic and, consequently, some environmental microorganisms have evolved mechanisms to detoxify MAs(III). However, the mechanisms of MAs(III) detoxification are not well understood. In this study, we identified an arsenic resistance ( ars ) operon consisting of three genes, arsRVK , that contribute to MAs(III) resistance in Ensifer adhaerens ST2. ArsV is annotated as an NADPH‐dependent flavin monooxygenase with unknown function. Expression of arsV in the arsenic hypersensitive Escherichia coli strain AW3110 Δars conferred resistance to MAs(III) and the ability to oxidize MAs(III) to MAs(V). In the presence of NADPH and either FAD or FMN, purified ArsV protein was able to oxidize both MAs(III) to MAs(V) and Sb(III) to Sb(V). Genes with arsV ‐like sequences are widely present in soils and environmental bacteria. Metagenomic analysis of five paddy soils showed the abundance of arsV ‐like sequences of 0.12–0.25 ppm. These results demonstrate that ArsV is a novel enzyme for the detoxification of MAs(III) and Sb(III) and the genes encoding ArsV are widely present in soil bacteria.

A community effort to assess and improve computerized interpretation of 12-lead resting electrocardiogram - Zijian Ding; Guijin Wang; Huazhong Yang; Ping Zhang; Dapeng Fu; Zhen Yang; Xinkang Wang; Xia Wang; Zhourui Xia; Chiming Zhang; Wenjie Cai; Binhang Yuan; et al. (Medical & Biological Engineering & Computing, 2022)
Computerized interpretation of electrocardiogram plays an important role in daily cardiovascular healthcare. However, inaccurate interpretations lead to misdiagnoses and delay proper treatments. In this work, we built a high-quality Chinese 12-lead resting electrocardiogram dataset with 15,357 records, and called for a community effort to improve the performances of CIE through the China ECG AI Contest 2019. This dataset covers most types of ECG interpretations, including the normal type, 8 common abnormal types, and the other type which includes both uncommon abnormal and noise signals. Based on the Contest, we systematically assessed and analyzed a set of top-performing methods, most of which are deep neural networks, with both their commonalities and characteristics. This study establishes the benchmarks for computerized interpretation of 12-lead resting electrocardiogram and provides insights for the development of new methods.

Laser ablation inductively coupled plasma mass spectrometry analysis of Chinese lead-barium glass: combining multivariate kernel density estimation and maximum mean discrepancy to reinterpret the raw glass used for producing lead-barium glass - Qian Ma; Rui Wen; Yifan Yu; Long Wang; Man Li; Luwu Cai; Li Ping; Zhiqiang Zhao; Dong Wang; Xiang Wang; Ruoyu Shi; A. Mark Pollard (Archaeological and Anthropological Sciences, 2022)

Isoquercitrin Upregulates Aldolase C Through Nrf2 to Ameliorate OGD/R-Induced Damage in SH-SY5Y Cells - Shi-Chang Cai; Chuan-An Yi; Xiang-Shang Hu; Gen-Yun Tang; Li-Ming Yi; Xiu-Ping Li (Neurotoxicity Research, 2021)

Dietary pectin caused great changes in bile acid profiles of Pelteobagrus fulvidraco - Xiamin Cao; Shengjie Ren; Chunfang Cai; Qin Ni; Xinyue Li; Yunhe Meng; Zijing Meng; Ye Shi; Huangen Chen; Rong Jiang; Ping Wu; Yuantu Ye (Fish Physiology and Biochemistry, 2021)

Two new cephalochromin derivative from the Alternaria sp. ZG22 - Xin-Ming Song; Xue-Ming Zhou; Ya-Ling Li; Li-Bing Huang; Cai-Cui Chen; Yan Gao; Lin He; Xiao-qun Mao; Bing Chen; Jing-Wen Liu; Hui-Jie Liu; Xiao-Ping Song; et al. (Natural Product Research, 2021)

Discovery of structural deletions in breast cancer predisposition genes using whole genome sequencing data from > 2000 women of African-ancestry - Zhishan Chen; Xingyi Guo; Jirong Long; Jie Ping; Bingshan Li; Mary Kay Fadden; Thomas U. Ahearn; Daniel O. Stram; Xiao-Ou Shu; Guochong Jia; Jonine Figueroa; Robertson Adjei; et al. (Human Genetics, 2021)

Migration and transformation of heavy metals in hyperaccumulators during the thermal treatment: a review - Wei Su; Xinyan Li; Hongshuo Zhang; Yi Xing; Ping Liu; Changqing Cai (Environmental Science and Pollution Research, 2021)

Size distributions and health risks of particle-bound toxic elements in the southeast coastland of China - Shui-Ping Wu; Xiang Li; Mei-Jun Cai; Yang Gao; Chao Xu; James J. Schwab; Chung-Shin Yuan (Environmental Science and Pollution Research, 2021)

Steroidal glycosides from the underground parts of Hosta ventricosa and their anti-inflammatory activities in mice - Hong-Biao Chu; Nan-Nan Li; Zong-Ping Zhang; Xiao-Yue Hu; Cai-Yun Yu; Lei Hua (Natural Product Research, 2021)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

Subcellular Localization of the D27 Protein in Sugarcane (Saccharum spp. Hybrids) Using an Optimized Protoplast Isolation, Purification, and Transient Gene Expression Protocol - Zhuan-di Wu; Xin Hu; Feng-gang Zan; Yong-bao Pan; David M. Burner; Zheng-ying Luo; Jia-yong Liu; Li-ping Zhao; Li Yao; Yong Zhao; Xin-long Liu; Hong-ming Xia; et al. (Sugar Tech, 2021)

Groundwater sources, flow patterns, and hydrochemistry of the Central Yinchuan Plain, China - Ying Li; Ping Wu; Xiao-Qin Huang; Bo Zhang; Zhao-Xiang Xu; Yang Li; Jie Li; Lu-Chen Wang; Yu-Fang Sun; Xu-Chen Meng; Cheng-Wen Wang; Zi-Zhao Cai (Hydrogeology Journal, 2021)

First report of cucumber mosaic virus infecting Morinda officinalis in China - Chong Feng; Ti-Jiang Shan; Li Yang; Miao-Miao Cai; De-Po Yang; Zhi-Min Zhao; Ping Ding (Journal of Plant Pathology, 2021)

Improved control of Frankliniella occidentalis on greenhouse pepper through the integration of Orius sauteri and neonicotinoid insecticides - Qing-cai Lin; Hao Chen; Dirk Babendreier; Jin-ping Zhang; Feng Zhang; Xiao-yan Dai; Zuo-wen Sun; Zhao-peng Shi; Xiao-lin Dong; Guang-an Wu; Yi Yu; Li Zheng; et al. (Journal of Pest Science, 2021)

Functional expression and characterization of an endo-1,4-β-mannosidase from Triticum aestivum in Pichia pastoris - Shuai-Bing Zhang; Wei-Ji Zhang; Na Li; Huan-Chen Zhai; Yang-Yong Lv; Yuan-Sen Hu; Jing-Ping Cai (Biologia, 2020)

Comparative iTRAQ Proteomics Reveals Multiple Effects of Selenium Yeast on Dairy Cows in Parturition - Zhi-hua Ren; Li-peng Bai; Liu-hong Shen; Zheng-zhong Luo; Zi-han Zhou; Zhi-cai Zuo; Xiao-ping Ma; Jun-liang Deng; Ya Wang; Sheng-yu Xu; Yu-heng Luo; Sui-zhong Cao; et al. (Biological Trace Element Research, 2020)

Sandstorm weather is a risk factor for mortality in ischemic heart disease patients in the Hexi Corridor, northwestern China - Xinghui Li; Hui Cai; Xiaolan Ren; Jin He; Jia Tang; Ping Xie; Nan Wang; Fangfei Nie; Linfeng Lei; Chenchen Wang; Wenli Li; Jing Ma (Environmental Science and Pollution Research, 2020)

The isolation and culture of giant panda (Ailuropoda melanoleuca) breast milk cells - Chen Yijiao; Wang Donghui; Liu Yuliang; Li Feiping; He Ping; Cai Zhigang; Zhang Hao; Chen Min; Hou Rong; An Junhui (In Vitro Cellular & Developmental Biology - Animal, 2020)

Predicting postmortem interval based on microbial community sequences and machine learning algorithms - Ruina Liu; Yuexi Gu; Mingwang Shen; Huan Li; Kai Zhang; Qi Wang; Xin Wei; Haohui Zhang; Di Wu; Kai Yu; Wumin Cai; Gongji Wang; et al. (Environmental Microbiology, 2020)
Summary Microbes play an essential role in the decomposition process but were poorly understood in their succession and behaviour. Previous researches have shown that microbes show predictable behaviour that starts at death and changes during the decomposition process. Research of such behaviour enhances the understanding of decomposition and benefits estimating the postmortem interval (PMI) in forensic investigations, which is critical but faces multiple challenges. In this study, we combined microbial community characterization, microbiome sequencing from different organs (i.e. brain, heart and cecum) and machine learning algorithms [random forest (RF), support vector machine (SVM) and artificial neural network (ANN)] to investigate microbial succession pattern during corpse decomposition and estimate PMI in a mouse corpse system. Microbial communities exhibited significant differences between the death point and advanced decay stages. Enterococcus faecalis , Anaerosalibacter bizertensis , Lactobacillus reuteri , and so forth were identified as the most informative species in the decomposition process. Furthermore, the ANN model combined with the postmortem microbial data set from the cecum, which was the best combination among all candidates, yielded a mean absolute error of 1.5 ± 0.8 h within 24‐h decomposition and 14.5 ± 4.4 h within 15‐day decomposition. This integrated model can serve as a reliable and accurate technology in PMI estimation.

PX Domain-Containing Kinesin KIF16B and Microtubule-Dependent Intracellular Movements - Bo-jie Li; Hao Chen; Su-su Jiang; Chu-yao Wang; Qin-hui Tuo; Shi-yin Long; Cai-ping Zhang; Duan-fang Liao (The Journal of Membrane Biology, 2020)

Prolonged Neo-Tethyan magmatic arc in Myanmar: evidence from geochemistry and Sr–Nd–Hf isotopes of Cretaceous mafic–felsic intrusions in the Banmauk–Kawlin area - Jin-Xiang Li; Wei-Ming Fan; Li-Yun Zhang; Tou-Ping Peng; Ya-Li Sun; Lin Ding; Fu-Long Cai; Kyaing Sein (International Journal of Earth Sciences, 2020)

Roles of PTBP1 in alternative splicing, glycolysis, and oncogensis - Wei Zhu; Bo-lun Zhou; Li-juan Rong; Li Ye; Hong-juan Xu; Yao Zhou; Xue-jun Yan; Wei-dong Liu; Bin Zhu; Lei Wang; Xing-jun Jiang; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2020)

Topographic controls on the annual runoff coefficient and implications for landscape evolution across semiarid Qilian Mountains, NE Tibetan Plateau - Shun Cai; Hao-peng Geng; Bao-tian Pan; Yang Hong; Li-ping Chen (Journal of Mountain Science, 2020)

Heme oxygenase-1 regulates autophagy through carbon–oxygen to alleviate deoxynivalenol-induced hepatic damage - Zhao Peng; Yuxiao Liao; Xiaoqian Wang; Liangkai Chen; Liangliang Wang; Chenyuan Qin; Zhenting Wang; Mengyao Cai; Jiawei Hu; Dan Li; Ping Yao; Andreas K. Nüssler; et al. (Archives of Toxicology, 2020)

Mechanistic examination of methimazole-induced hepatotoxicity in patients with Grave’s disease: a metabolomic approach - Xuesong Li; Jialin Yang; Shasha Jin; Yu Dai; Yujuan Fan; Xiaofang Fan; Zhigang Li; Jianhua Yang; Wai-Ping Yau; Haishu Lin; Weimin Cai; Xiaoqiang Xiang (Archives of Toxicology, 2020)

New anthraquinone and eurotinone analogue from the seeds of Senna obtusifolia and their inhibitory effects on human organic anion transporters 1 and 3 - Xu Pang; Li-Ming Wang; You-Cai Zhang; Li-Ping Kang; He-Shui Yu; Guan-Wei Fan; Li-Feng Han (Natural Product Research, 2019)

Synthesis and biological evaluation of novel disulfides incorporating 1,3,4-thiadiazole scaffold as promising antitumor agents - Sha Li; Hai-Xin Wang; Hai-Ying Liu; Fen Jing; Xiao-Yun Fu; Cai-Wen Li; Yan-Ping Shi; Bao-Quan Chen (Medicinal Chemistry Research, 2019)

Recent research progress in geochemical properties and restoration of heavy metals in contaminated soil by phytoremediation - Jiang-tao Fu; Dong-mei Yu; Xi Chen; Ying Su; Cai-hong Li; Yong-ping Wei (Journal of Mountain Science, 2019)

Relationship between stand characteristics and soil properties of two typical forest plantations in the mountainous area of Western Sichuan, China - Hao Yang; Ning Miao; Shao-cai Li; Rui Ma; Zi-yan Liao; Wei-ping Wang; Hai-long Sun (Journal of Mountain Science, 2019)

New adenine analogues and a pyrrole alkaloid from Selaginella delicatula - Cai-Ping Yao; Zhen-Xing Zou; Yan Zhang; Jing Li; Fei Cheng; Ping-Sheng Xu; Gan Zhou; Xiao-Min Li; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2019)

Regulation of T cell differentiation and function by epigenetic modification enzymes - Huicheng Liu; Pingfei Li; Zhengping Wei; Cai Zhang; Minghui Xia; Qiuyang Du; Yufei Chen; Na Liu; Huabin Li; Xiang-Ping Yang (Seminars in Immunopathology, 2019)

Attribute recognition model for risk assessment of water inrush - Jing Wang; Shu-cai Li; Li-ping Li; Peng Lin; Zhen-hao Xu; Cheng-lu Gao (Bulletin of Engineering Geology and the Environment, 2019)

Molecular and Functional Characterization of ZmNF-YC14 in Transgenic Arabidopsis - Xiupeng Mei; Ping Li; Lu Wang; Chaoxian Liu; Lian Zhou; Yilin Cai (Journal of Plant Biology, 2018)

A new12-membered lactone from the stems of Ficus auriculata - Tai-Ming Shao; Cai-Juan Zheng; Xiao-Bao Li; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han (Natural Product Research, 2018)

A New Advance Classification Method for Surrounding Rock in Tunnels Based on the Set-Pair Analysis and Tunnel Seismic Prediction System - Lin Bu; Shu-cai Li; Shao-shuai Shi; Xiao-kun Xie; Li-ping Li; Zong-qing Zhou; Zhi-jie Wen (Geotechnical and Geological Engineering, 2018)

Design of a Displacement Monitoring System Based on Optical Grating and Numerical Verification in Geomechanical Model Test of Water Leakage of Tunnel - Shang-qu Sun; Shu-cai Li; Li-ping Li; Shao-shuai Shi; Zong-qing Zhou; Cheng-lu Gao (Geotechnical and Geological Engineering, 2018)

Segmentation by domestic visitor motivation: Changbai Mountain Biosphere Reserve, China - Xiao-ping Gu; Bernard J. Lewis; Li-jun Niu; Da-pao Yu; Li Zhou; Wang-ming Zhou; Zhen-cai Gong; Zhi-juan Tai; Li-min Dai (Journal of Mountain Science, 2018)

Transcriptome analysis of wheat seedling and spike tissues in the hybrid Jingmai 8 uncovered genes involved in heterosis - Yong-jie Liu; Shi-qing Gao; Yi-miao Tang; Jie Gong; Xiao Zhang; Yong-bo Wang; Li-ping Zhang; Ren-wei Sun; Quan Zhang; Zhao-bo Chen; Xiang Wang; Cai-juan Guo; et al. (Planta, 2018)

The Risk Assessment of Tunnels Based on Grey Correlation and Entropy Weight Method - Cheng-lu Gao; Shu-cai Li; Jing Wang; Li-ping Li; Peng Lin (Geotechnical and Geological Engineering, 2018)

Effect of UGT2B7 genotypes on plasma concentration of valproic acid: a meta-analysis - Ping Wang; Xiao-Qian Lin; Wen-Ke Cai; Gui-Li Xu; Meng-Di Zhou; Mei Yang; Gong-Hao He (European Journal of Clinical Pharmacology, 2018)

Nonlinear analysis of the response of a single pile subjected to tension load using a hyperbolic model - Shuai Cheng; Qian-qing Zhang; Shu-cai Li; Li-ping Li; Shi-min Zhang; Kang Wang (European Journal of Environmental and Civil Engineering, 2018)

Molecular diversity of phenothiazines: design and synthesis of phenothiazine–dithiocarbamate hybrids as potential cell cycle blockers - Dong-Jun Fu; Ruo-Han Zhao; Jia-Huan Li; Jia-Jia Yang; Ruo-Wang Mao; Bo-Wen Wu; Ping Li; Xiao-Lin Zi; Qing-Qing Zhang; Hui-Jie Cai; Sai-Yang Zhang; Yan-Bing Zhang; et al. (Molecular Diversity, 2017)

The biogeographical distribution of tree species-abundance and its relation to climatic factors in mass islands - Xiaoming Li; Chengzhen Wu; Wu Gu; Ran Ye; Haibo Zhang; Ping Qi; Shengqiang Wang; Siying Zhou; Yongjie Wei; Yanhong Cai (Acta Oceanologica Sinica, 2017)

Identification of Novel Compound Mutations in PLA2G6-Associated Neurodegeneration Patient with Characteristic MRI Imaging - Sen Guo; Liu Yang; Huijie Liu; Wei Chen; Jinchen Li; Ping Yu; Zhong Sheng Sun; Xiang Chen; Jie Du; Tao Cai (Molecular Neurobiology, 2017)

Rockfall Hazard Assessment on Wangxia Rock Mass in Wushan (Chongqing, China) - Shang-qu Sun; Li-ping Li; Shu-cai Li; Qian-qing Zhang; Cong Hu (Geotechnical and Geological Engineering, 2017)

Overexpression of Arabidopsis ICR1 gene affects vegetative growth and anthesis - Da-Hui Li; Man-Li Li; Xiao-Bo Yu; Di Wu; Huan Xi; Yi Lin; Yong-Ping Cai (Biologia, 2017)

TGF-β1-miR-200a-PTEN induces epithelial–mesenchymal transition and fibrosis of pancreatic stellate cells - Min Xu; Guoying Wang; Hailang Zhou; Jing Cai; Ping Li; Meng Zhou; Ying Lu; Xiaomeng Jiang; Hongmei Huang; Youli Zhang; Aihua Gong (Molecular and Cellular Biochemistry, 2017)

One new lignan derivative from the Combretum alfredii Hance - Meng Bai; Li-Jun Wu; Yue Cai; Shou-Yuan Wu; Xiao-Ping Song; Guang-Ying Chen; Cai-Juan Zheng; Chang-Ri Han (Natural Product Research, 2017)

Interaction between southern rice black-streaked dwarf virus minor core protein P8 and a rice zinc finger transcription factor - Jing Li; Nian-Jun Cai; Jin Xue; Jian Yang; Jian-Ping Chen; Heng-Mu Zhang (Archives of Virology, 2017)

Di (2-ethylhexyl) phthalate impairs steroidogenesis in ovarian follicular cells of prepuberal mice - Fang-Nong Lai; Jing-Cai Liu; Lan Li; Jun-Yu Ma; Xue-Lian Liu; Yu-Ping Liu; Xi-Feng Zhang; Hong Chen; Massimo De Felici; Paul W. Dyce; Wei Shen (Archives of Toxicology, 2017)

Mice lacking myotubularin-related protein 14 show accelerated high-fat diet-induced lipid accumulation and inflammation - Lv Yin; Peng Yong-bo; Yu Meng-Fei; Chen Weiwei; Zhao Ping; Xue Lu; Ma Li-Qun; Cai Congli; Liu Qing-hua; Shen Jinhua (Journal of Physiology and Biochemistry, 2017)

Improvement of anti-nutritional effect resulting from β-glucanase specific expression in the parotid gland of transgenic pigs - Li-zeng Guan; Jin-shun Cai; Shuai Zhao; Yu-ping Sun; Jing-lan Wang; Yong Jiang; Gang Shu; Qing-yan Jiang; Zhen-fang Wu; Qian-yun Xi; Yong-liang Zhang (Transgenic Research, 2017)

Fine mapping and candidate gene analysis of two loci conferring resistance to Phytophthora sojae in soybean - Linghong Li; Feng Lin; Weidong Wang; Jieqing Ping; Joshua C. Fitzgerald; Meixia Zhao; Shuai Li; Lianjun Sun; Chunmei Cai; Jianxin Ma (Theoretical and Applied Genetics, 2016)

Development of chloroplast genomic resources for Akebia quinata (Lardizabalaceae) - Bin Li; Yanda Li; Qifei Cai; Furong Lin; Ping Huang; Yongqi Zheng (Conservation Genetics Resources, 2016)

Changes in subcellular distribution and antioxidant compounds involved in Pb accumulation and detoxification in Neyraudia reynaudiana - Chuifan Zhou; Meiying Huang; Ying Li; Jiewen Luo; Li ping Cai (Environmental Science and Pollution Research, 2016)

One new berberine from the branches and leaves of Polyalthia obliqua Hook.f. & Thomson - Li-Jun Wu; Cai-Juan Zheng; Liu-Kai Wang; Chang-Ri Han; Xiao-Ping Song; Guang-Ying Chen; Xue-ming Zhou; Shou-yuan Wu; Xiao-bao Li; Meng Bai; Chun-xin Liu; Jun Yao (Natural Product Research, 2016)

Characterization and expression analysis of cDNAs encoding abscisic acid 8′-hydroxylase during mulberry fruit maturation and under stress conditions - Yuxiang Cai; Panpan Zhu; Changying Liu; Aichun Zhao; Jian Yu; Chuanhong Wang; Zhengang Li; Ping Huang; Maode Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Netrin-1 Contributes to Myelinated Afferent Fiber Sprouting and Neuropathic Pain - Cai-Hua Wu; Xiao-Cui Yuan; Fang Gao; Hong-Ping Li; Jie Cao; Yan-Shen Liu; Wei Yu; Bo Tian; Xian-Fang Meng; Jing Shi; Hui-Lin Pan; Man Li (Molecular Neurobiology, 2016)

Flavonoids of Rosa roxburghii Tratt exhibit radioprotection and anti-apoptosis properties via the Bcl-2(Ca2+)/Caspase-3/PARP-1 pathway - Ping Xu; Xinhua Cai; Wenbo Zhang; Yana Li; Peiyong Qiu; Dandan Lu; Xiaoyang He (Apoptosis, 2016)

Activation of phenylpropanoid pathway and PR of potato tuber against Fusarium sulphureum by fungal elicitor from Trichothecium roseum - Xiao-yan Yu; Yang Bi; Lu Yan; Xiao Liu; Yi Wang; Ke-ping Shen; Yong-cai Li (World Journal of Microbiology and Biotechnology, 2016)

Tight regulation of the interaction between Brassica napus and Sclerotinia sclerotiorum at the microRNA level - Jia-Yi Cao; You-Ping Xu; Li Zhao; Shuang-Sheng Li; Xin-Zhong Cai (Plant Molecular Biology, 2016)

Epidemiology of Superficial Fungal Infections in Guangdong, Southern China: A Retrospective Study from 2004 to 2014 - Wenying Cai; Changming Lu; Xiqing Li; Junmin Zhang; Ping Zhan; Liyan Xi; Jiufeng Sun; Xinbing Yu (Mycopathologia, 2016)

Analysis and Construction Techniques for a Water Seal for Underground Mines Subjected to Water Inrush - Shu-cai Li; Fei Xu; Qian-qing Zhang; Li-ping Li; Wei-ming Wang; Hong-liang Liu (Mine Water and the Environment, 2016)

A new phenolic compound with antioxidant activity from the branches and leaves of Pyrus pashia - Zhen-Jie Li; Xi Zheng; Chun-Ping Wan; Le Cai; Ying Li; Lin Huang; Zhong-Tao Ding (Natural Product Research, 2016)

Study on Longitudinal Deformation Profile of Rock Mass in a Subsea Tunnel - Shu-Guang Song; Shu-Cai Li; Li-Ping Li; Qian-Qing Zhang; Kai Wang; Yi Zhou; Hong-Liang Liu (Marine Georesources & Geotechnology, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Analysis and Design Implications on Stability of Cofferdam Subjected to Water Wave Action - Fei Xu; Shu-Cai Li; Qian-Qing Zhang; Li-Ping Li; Qian Zhang; Kang Wang; Hong-Liang Liu (Marine Georesources & Geotechnology, 2016)

Canonical and non-canonical Wnt signaling control the regeneration of amputated rodent vibrissae follicles - Yan-Ping Yuan; Keng Huang; Yan-Min Xu; Xian-Cai Chen; Hai-Hong Li; Bo-Zhi Cai; Yang Liu; Huan Zhang; Yu Li; Chang-Min Lin (Journal of Molecular Histology, 2016)

Field and Theoretical Study of the Response of Super-Long Bored Pile Subjected to Compressive Load - Shu-cai Li; Qian Zhang; Qian-qing Zhang; Li-ping Li (Marine Georesources & Geotechnology, 2016)

Growth trajectories and interspecific competitive dynamics in wheat/maize and barley/maize intercropping - Wei-Ping Zhang; Guang-Cai Liu; Jian-Hao Sun; Li-Zhen Zhang; Jacob Weiner; Long Li (Plant and Soil, 2015)

Clinical, biochemical, neuroimaging and molecular findings of X-linked Adrenoleukodystrophy patients in South China - Min-yan Jiang; Yan-na Cai; Cui-li Liang; Min-zhi Peng; Hui-ying Sheng; Li-ping Fan; Rui-zhu Lin; Hua Jiang; Yonglan Huang; Li Liu (Metabolic Brain Disease, 2015)

Hydrogen peroxide is indispensable to Xanthomonas oryzae pv. oryzae-induced hypersensitive response and nonhost resistance in Nicotiana benthamiana - Wen Li; You-Ping Xu; Juan Yang; Gong-You Chen; Xin-Zhong Cai (Australasian Plant Pathology, 2015)

Isolation of a new flavanone from Daidai fruit and hypolipidemic activity of total flavonoids extracts - Ling-Jun Zeng; Dan Chen; Qing-De Huang; Qun Huang; Yun-Fang Lian; Wei-Wei Cai; Hua-Ping Zeng; Yi-Li Lin (Natural Product Research, 2015)

A new bibenzyl derivative with nuclear factor-kappaB inhibitory activity from Schefflera arboricola (Araliaceae) - Hang Li; Zi-Zhe Cai; Long-Ping Zhu; Xin-Jun Xu; Shao-Rui Chen; De-Po Yang; Zhi-Min Zhao (Natural Product Research, 2015)

Expression of Wnt/β-catenin signaling, stem-cell markers and proliferating cell markers in rat whisker hair follicles - Chang-min Lin; Yan-ping Yuan; Xian-cai Chen; Hai-hong Li; Bo-zhi Cai; Yang Liu; Huan Zhang; Yu Li; Keng Huang (Journal of Molecular Histology, 2015)

West Eurasian mtDNA lineages in India: an insight into the spread of the Dravidian language and the origins of the caste system - Malliya Gounder Palanichamy; Bikash Mitra; Cai-Ling Zhang; Monojit Debnath; Gui-Mei Li; Hua-Wei Wang; Suraksha Agrawal; Tapas Kumar Chaudhuri; Ya-Ping Zhang (Human Genetics, 2015)

The aflatoxin-detoxifizyme specific expression in mouse parotid gland - Li-zeng Guan; Yu-ping Sun; Jin-shun Cai; Han-dong Wu; Long-zheng Yu; Yong-liang Zhang; Qian-yun Xi (Transgenic Research, 2015)

Predicting hybrid fertility from maker-based genetic divergence index of parental varieties: implications for utilizing inter-subspecies heterosis in hybrid rice breeding - Ping Liu; Zhiwu Dan; Zhe Wang; Shaoqing Li; Nengwu Li; Huanxin Yan; Xingxing Cai; Bao-Rong Lu (Euphytica, 2015)

Analysis on Response of a Single Pile Subjected to Tension Load Using a Softening Model and a Hyperbolic Model - Qian-Qing Zhang; Shu-Cai Li; Qian Zhang; Li-Ping Li; Bo Zhang (Marine Georesources & Geotechnology, 2015)

Genetic manipulation of a high-affinity PHR1 target cis-element to improve phosphorous uptake in Oryza sativa L. - Wenyuan Ruan; Meina Guo; Linlin Cai; Hongtao Hu; Changying Li; Yu Liu; Zhongchang Wu; Chuanzao Mao; Keke Yi; Ping Wu; Xiaorong Mo (Plant Molecular Biology, 2015)

Three-dimensional tensor controlled-source electromagnetic modeling based on the vector finite-element method - Ying-Cai Hu; Tong-Lin Li; Cui-Song Fan; Da-Yong Wang; Jian-Ping Li (Applied Geophysics, 2015)

RGD-conjugated solid lipid nanoparticles inhibit adhesion and invasion of αvβ3 integrin-overexpressing breast cancer cells - Dan Shan; Jason Li; Ping Cai; Preethy Prasad; Franky Liu; Andrew Michael Rauth; Xiao Yu Wu (Drug Delivery and Translational Research, 2015)

Field and Theoretical Analysis on the Response of Destructive Pile Subjected to Tension Load - Qian-Qing Zhang; Shu-Cai Li; Li-Ping Li (Marine Georesources & Geotechnology, 2015)

Contamination of commercially available seafood by key diarrhetic shellfish poisons along the coast of China - Chao Lin; Zeng-Shan Liu; Cai-Yun Tan; Yi-Ping Guo; Lin Li; Hong-Lin Ren; Yan-Song Li; Pan Hu; Sheng Gong; Yu Zhou; Shi-Ying Lu (Environmental Science and Pollution Research, 2015)

Association of IL-18 promoter gene polymorphisms with rheumatoid arthritis: a meta-analysis - Li-Ping Cai; Li-Juan Zhou; Shun-Yu Lu; Ying-E Liang; Xiao-Ying Chen; Lin Liu; Jun Lin (Molecular Biology Reports, 2014)

Isolation and molecular characterization of an ethylene response factor NtERF1-1 in Nicotiana tabacum cv. Xanthi - Jun-Shan Gao; Li Hu; Peng Xie; Yan Meng; Yong-Ping Cai; Yi Lin (Journal of Biosciences, 2014)

The source apportionment of polycyclic aromatic hydrocarbons (PAHs) in the topsoil in Xiaodian sewage irrigation area, North of China - Jia-Le Li; Yan-Xin Wang; Cai-Xiang Zhang; Yi-Hui Dong; Bin Du; Xiao-Ping Liao (Ecotoxicology, 2014)

Isolation and characterization of polymorphic microsatellites in the perennial herb Euphorbia kansui using paired-end Illumina shotgun sequencing - Xiao-Hao Yan; Min-Feng Fang; Zeng-Qiang Qian; Zhan-Lin Liu; Ma-Li Wang; Cai-Ping Tian; Meng-Han Du; Yin-Jun Li; Zhong-Hu Li; Gui-Fang Zhao (Conservation Genetics Resources, 2014)

The rescuable function and mechanism of resveratrol on As2O3-induced hERG K+ channel deficiency - Xin Zhao; Kai-ping Zhang; Ting Huang; Cai-Chuan Yan; Li-Rong Liu; Qi-Lei Zhu; Feng-Feng Guo; Chen Liu; Bao-Xin Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

IL-17A promotes ventricular remodeling after myocardial infarction - Su-Feng Zhou; Jing Yuan; Meng-Yang Liao; Ni Xia; Ting-Ting Tang; Jing-Jing Li; Jiao Jiao; Wen-Yong Dong; Shao-Fang Nie; Zheng-Feng Zhu; Wen-Cai Zhang; Bing-Jie Lv; et al. (Journal of Molecular Medicine, 2014)

Dysregulation of vitamin D metabolism in the brain and myocardium of rats following prolonged exposure to dexamethasone - Pei Jiang; Ying Xue; Huan-De Li; Yi-Ping Liu; Hua-Lin Cai; Mi-Mi Tang; Li-Hong Zhang (Psychopharmacology, 2014)

Neuroprotective effect of schizandrin A on oxygen and glucose deprivation/reperfusion-induced cell injury in primary culture of rat cortical neurons - Cai-Ping Wang; Gui-Cai Li; Yun-Wei Shi; Xiao-Chuan Zhang; Jian-Long Li; Zhi-Wei Wang; Fei Ding; Xin-Miao Liang (Journal of Physiology and Biochemistry, 2014)

Bernoulli-based random undersampling schemes for 2D seismic data regularization - Rui Cai; Qun Zhao; De-Ping She; Li Yang; Hui Cao; Qin-Yong Yang (Applied Geophysics, 2014)

Promoters of HcTPS1 and HcTPS2 Genes from Hedychium coronarium Direct Floral-Specific, Developmental-Regulated and Stress-Inducible Gene Expression in Transgenic Tobacco - Xin-Yue Li; Shao-Yuan Zheng; Rang-Cai Yu; Yan-Ping Fan (Plant Molecular Biology Reporter, 2014)

miRNAs expression profile in bast of ramie elongation phase and cell wall thickening and end wall dissolving phase - Jun Wang; Jing-shu Huang; Xin-yan Hao; Yan-ping Feng; Ya-Jun Cai; Li-qin Sun (Molecular Biology Reports, 2014)

Morphological and molecular evidence for a new species of Rhodotus from tropical and subtropical Yunnan, China - Li-Ping Tang; Yan-Jia Hao; Qing Cai; Bau Tolgor; Zhu L. Yang (Mycological Progress, 2014)

Field Study on the Behavior of Destructive and Non-Destructive Piles Under Compression - Qian-qing Zhang; Shu-Cai Li; Li-Ping Li (Marine Georesources & Geotechnology, 2014)

ROCK is Involved in Vimentin Phosphorylation and Rearrangement Induced by Dengue Virus - Shun Lei; Yan-Ping Tian; Wei-Dong Xiao; Shu Li; Xian-Cai Rao; Jun-Lei Zhang; Jie Yang; Xiao-Mei Hu; Wei Chen (Cell Biochemistry and Biophysics, 2013)

Two new vinblastine-type N -oxide alkaloids from Catharanthus roseus - Wei-Ku Zhang; Jie-Kun Xu; Hai-Yan Tian; Lei Wang; Xiao-Qi Zhang; Xu-Zhi Xiao; Ping Li; Wen-Cai Ye (Natural Product Research, 2013)

Identification and Expression Profiles of IL-8 in Bighead Carp (Aristichthys nobilis) in Response to Microcystin-LR - Huiying Li; Yan Cai; Ping Xie; Guangyu Li; Le Hao; Qian Xiong (Archives of Environmental Contamination and Toxicology, 2013)

DNA methylation alterations of upland cotton (Gossypium hirsutum) in response to cold stress - Hong Hong Fan; Jun Wei; Ting Chun Li; Zheng Peng Li; Ning Guo; Yong Ping Cai; Yi Lin (Acta Physiologiae Plantarum, 2013)

Label-free quantitative proteomics analysis of dormant terminal buds of poplar - De-Li Ning; Chang-Cai Liu; Jin-Wen Liu; Zhuo Shen; Su Chen; Feng Liu; Bai-Chen Wang; Chuan-Ping Yang (Molecular Biology Reports, 2013)

Warnstorfia exannulata, an aquatic moss in the Arctic: seasonal growth responses - Cai-Qing Guo; Ryszard Ochyra; Peng-Cheng Wu; Rodney D. Seppelt; Yi-Feng Yao; Lin-Gen Bian; Su-Ping Li; Cheng-Sen Li (Climatic Change, 2013)

Lack of effect of continuous glycyrrhizin administration on the pharmacokinetics of the P-glycoprotein substrate talinolol in healthy volunteers - Miao Yan; Ping-Fei Fang; Huan-De Li; Ping Xu; Yi-Ping Liu; Feng Wang; Hua-Lin Cai; Qin-You Tan (European Journal of Clinical Pharmacology, 2013)

Wnt/β-catenin signaling induces the aging of mesenchymal stem cells through promoting the ROS production - Da-yong Zhang; Yu Pan; Chong Zhang; Bing-xi Yan; Shan-shan Yu; Dong-ling Wu; Meng-meng Shi; Kai Shi; Xin-xiao Cai; Shuang-shuang Zhou; Jun-bo Wang; Jian-ping Pan; et al. (Molecular and Cellular Biochemistry, 2013)

Enhanced overall resistance to Fusarium seedling blight and Fusarium head blight in transgenic wheat by co-expression of anti-fungal peptides - Zheng-Wei Liu; He-Ping Li; Wei Cheng; Peng Yang; Jing-Bo Zhang; An-Dong Gong; Yan-Ni Feng; W. G. Dilantha Fernando; Yu-Cai Liao (European Journal of Plant Pathology, 2012)

Development of a substrate-coupled biocatalytic process driven by an NADPH-dependent sorbose reductase from Candida albicans for the asymmetric reduction of ethyl 4-chloro-3-oxobutanoate - Ping Cai; Mingdong An; Lin Xu; Sheng Xu; Ning Hao; Yan Li; Kai Guo; Ming Yan (Biotechnology Letters, 2012)

Comparative analysis of essential oil components of Evodia rutaecarpa (Juss.) Benth. var. officinalis (Dode) Huang and Evodia rutaecarpa (Juss.) Benth. - Guang-Xian Cai; Dan Huang; Shun-Xiang Li; Fei Xu; Lu Wang; Yan-Hui Lu; Liang Cao; Bao-Yang Wei; Ya Li; Ping Cai (Natural Product Research, 2012)

Lipoxin A4 Inhibits 5-Lipoxygenase Translocation and Leukotrienes Biosynthesis to Exert a Neuroprotective Effect in Cerebral Ischemia/Reperfusion Injury - Le Wu; Sen Miao; Lin-Bing Zou; Ping Wu; Hua Hao; Ke Tang; Pan Zeng; Jing Xiong; Hong-Hua Li; Qiang Wu; Lei Cai; Du-Yun Ye (Journal of Molecular Neuroscience, 2012)

Genome-wide Identification and Characterization of a Dehydrin Gene Family in Poplar (Populus trichocarpa) - Chang-Cai Liu; Chun-Ming Li; Bao-Guang Liu; Su-Jie Ge; Xiu-Mei Dong; Wei Li; Hang-Yong Zhu; Bai-Chen Wang; Chuan-Ping Yang (Plant Molecular Biology Reporter, 2012)

Response to weaning and dietary l-glutamine supplementation: metabolomic analysis in piglets by gas chromatography/mass spectrometry - Ying-ping Xiao; Tian-xing Wu; Qi-hua Hong; Jiang-ming Sun; An-guo Chen; Cai-mei Yang; Xiao-yan Li (Journal of Zhejiang University-SCIENCE B, 2012)

Clinical significance of peritumoral lymphatic vessel density and lymphatic vessel invasion detected by D2-40 immunostaining in FIGO Ib1-IIa squamous cell cervical cancer - Ying Xiong; Li-Ping Cao; Hui-Lan Rao; Mu-Yan Cai; Li-Zhi Liang; Ji-Hong Liu (Cell and Tissue Research, 2012)

Gene expression profiling of Sinapis alba leaves under drought stress and rewatering growth conditions with Illumina deep sequencing - Cai-Hua Dong; Chen Li; Xiao-Hong Yan; Shun-Mou Huang; Jin-Yong Huang; Li-Jun Wang; Rui-Xing Guo; Guang-Yuan Lu; Xue-Kun Zhang; Xiao-Ping Fang; Wen-Hui Wei (Molecular Biology Reports, 2012)

Lowered Nudix type 5 (NUDT5) expression leads to cell cycle retardation in HeLa cells - Li-Qun Zhang; Da-Peng Dai; Wei Gan; Yasumitsu Takagi; Hiroshi Hayakawa; Mutsuo Sekiguchi; Jian-Ping Cai (Molecular and Cellular Biochemistry, 2012)

Physiological responses to salt stress of T2 alfalfa progenies carrying a transgene for betaine aldehyde dehydrogenase - Li-Ping Yan; Cui-Lan Liu; Hui-Min Liang; Xiu-Hong Mao; Fei Wang; Cai-Hong Pang; Jing Shu; Yang Xia (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Protein sequence analysis based on hydropathy profile of amino acids - Xiao-li Xie; Li-fei Zheng; Ying Yu; Li-ping Liang; Man-cai Guo; John Song; Zhi-fa Yuan (Journal of Zhejiang University-SCIENCE B, 2012)

Synthesis of (–)-arctigenin derivatives and their anticancer activity - Chen Gui-Rong; Cai Li-Ping; Dou De-Qiang; Kang Ting-Guo; Li Hong-Fu; Li Fu-Rui; Jiang Ning (Natural Product Research, 2012)

Effects of insulin-like growth factor-1 on the properties of mesenchymal stem cells in vitro - Yu-li Huang; Ruo-feng Qiu; Wei-yi Mai; Jian Kuang; Xiao-yan Cai; Yu-gang Dong; Yun-zhao Hu; Yuan-bin Song; An-ping Cai; Zhi-gao Jiang (Journal of Zhejiang University-SCIENCE B, 2012)

Maohuoside A promotes osteogenesis of rat mesenchymal stem cells via BMP and MAPK signaling pathways - Lei Yang; Nai-Li Wang; Guo-Ping Cai (Molecular and Cellular Biochemistry, 2011)

Sex difference in QTc prolongation in chronic institutionalized patients with schizophrenia on long-term treatment with typical and atypical antipsychotics - Fu De Yang; Xiang Qun Wang; Xiu Ping Liu; Ke Xin Zhao; Wei Hong Fu; Xue Ru Hao; Xing Li Zhang; Guo Shu Huang; Sheng Cai Qu; Jing Shen Bai; Xu Feng Huang; Thomas R. Kosten; et al. (Psychopharmacology, 2011)

Protection of CHO cells by transfer of survivin driven by ovarian-specific promoter OSP-2 - Chun-Hua Tu; Wei-Peng Liu; Mei Dong; Li-Ping Cai; Ya-Qin Mo; Dong-Zi Yang (Molecular Biology Reports, 2011)

Isolation and characterization of a gene encoding a polyethylene glycol-induced cysteine protease in common wheat - Qing-Wei Zang; Cai-Xiang Wang; Xu-Yan Li; Zhi-Ai Guo; Rui-Lian Jing; Jun Zhao; Xiao-Ping Chang (Journal of Biosciences, 2010)

Do local communities support the conservation of endangered Przewalski’s gazelle? - Junhua Hu; Xiaoge Ping; Jing Cai; Zhongqiu Li; Chunwang Li; Zhigang Jiang (European Journal of Wildlife Research, 2010)

Chloroplast transformation of rapeseed (Brassica napus) by particle bombardment of cotyledons - Lin Cheng; He-Ping Li; Bo Qu; Tao Huang; Jin-Xing Tu; Ting-Dong Fu; Yu-Cai Liao (Plant Cell Reports, 2010)

Allopatric divergence and phylogeographic structure of the plateau zokor ( Eospalax baileyi ), a fossorial rodent endemic to the Qinghai–Tibetan Plateau - Li‐Zhou Tang; Liu‐Yang Wang; Zhen‐Yuan Cai; Tong‐Zuo Zhang; Hai‐Xin Ci; Gong‐Hua Lin; Jian‐Ping Su; Jian‐Quan Liu (Journal of Biogeography, 2010)
Aim Most species of temperate regions are believed to have shifted to lower latitudes or elevations during the glacial periods of the Quaternary. In this study we test whether this phylogeographic assumption is also true for the plateau zokor ( Eospalax baileyi ), a fossorial rodent endemic to the climate‐sensitive Qinghai–Tibetan Plateau (QTP), which ranges in elevation from 2600 to 4600 m. Location The QTP of western China. Methods Phylogeographic analyses were conducted based on the mitochondrial cytochrome b gene sequences of 193 individuals from 20 populations over the entire range of the species. Results A total of 54 haplotypes identified in the present study clustered into four geographically correlated clades located in the interior of the QTP (clade A) and at the plateau edge (B, C and D). Molecular calibrations suggest that the interior plateau (A) and plateau‐edge (B–D) clades diverged at 1.2 Ma and that the three plateau‐edge clades diverged between 0.85 and 0.80 Ma. These estimates are concordant with diastrophism and glaciation events in the QTP. Coalescent tests rejected both the hypothesis that all current populations originated from a single refugium at a low elevation during the Last Glacial Maximum (LGM) and the hypothesis that the two lineages diverged during the LGM. The tests instead supported the hypothesis that there were four refugia during the LGM, and that the four clades diverged prior to the late Pleistocene. Main conclusions Our results suggest that Quaternary diastrophisms and glaciations repeatedly promoted allopatric divergence of the plateau zokor into geographical clades, and that these regional clades subsequently persisted at high elevations, rather than migrating to the low‐elevation plateau edge during subsequent glacial ages.

Isolation of a new glycoside from starfish, Asterias amurensis Lutken, and its stimulation activity on the proliferation of the UMR106 cell - Hong-Wei Liu; Jian-Kuan Li; Da-Wei Zhang; Jing-Chao Zhang; Xue Zhang; Xiao-Hong Song; Ying Xia; Nai-Li Wang; Xin-Sheng Yao; Guo-Ping Cai (Natural Product Research, 2010)

Phosphoproteomic identification and phylogenetic analysis of ribosomal P-proteins in Populus dormant terminal buds - Chang-Cai Liu; Tian-Cong Lu; Hua-Hua Li; Hong-Xia Wang; Gui-Feng Liu; Ling Ma; Chuan-Ping Yang; Bai-Chen Wang (Planta, 2010)

Drepanocladus longifolius (Amblystegiaceae), an addition to the moss flora of King George Island, South Shetland Islands, with a review of Antarctic benthic mosses - Su-Ping Li; Ryszard Ochyra; Peng-Cheng Wu; Rodney D. Seppelt; Ming-Hong Cai; Hai-Ying Wang; Cheng-Sen Li (Polar Biology, 2009)

A surface plasmon resonance-based solution affinity assay for heparan sulfate-binding proteins - Siska Cochran; Cai Ping Li; Vito Ferro (Glycoconjugate Journal, 2009)

The effects of land use change on environmental quality in the red soil hilly region, China: A case study in Xianning County - Zhi-Hua Shi; Li-Ding Chen; Jun-Ping Hao; Tian-Wei Wang; Chong-Fa Cai (Environmental Monitoring and Assessment, 2009)

Triptolide protects against 1-methyl-4-phenyl pyridinium-induced dopaminergic neurotoxicity in rats: Implication for immunosuppressive therapy in Parkinson’s disease - Jun-Peng Gao; Shan Sun; Wen-Wei Li; Yi-Ping Chen; Ding-Fang Cai (Neuroscience Bulletin, 2008)

Characterization of cDNAs associated with lignification and their expression profiles in loquat fruit with different lignin accumulation - Lan Lan Shan; Xian Li; Ping Wang; Chong Cai; Bo Zhang; Chong De Sun; Wang Shu Zhang; Chang Jie Xu; Ian Ferguson; Kun Song Chen (Planta, 2008)

Evidence of Gene Conversion in the Evolutionary Process of the Codon 41/42 (-CTTT) Mutation Causing β-Thalassemia in Southern China - Wen Zhang; Wang-Wei Cai; Wei-Ping Zhou; Hai-Peng Li; Liang Li; Wei Yan; Qin-Kai Deng; Ya-Ping Zhang; Yun-Xin Fu; Xiang-Min Xu (Journal of Molecular Evolution, 2008)

Identification of label-retaining cells in nasopharyngeal epithelia and nasopharyngeal carcinoma tissues - Hong-Bo Zhang; Cai-Ping Ren; Xu-Yu Yang; Lei Wang; Hui Li; Ming Zhao; Hong Yang; Kai-Tai Yao (Histochemistry and Cell Biology, 2007)

Ciona intestinalis as an emerging model organism: Its regeneration under controlled conditions and methodology for egg dechorionation - Li-ping Liu; Jian-hai Xiang; Bo Dong; Pavanasam Natarajan; Kui-jie Yu; Nan-er Cai (Journal of Zhejiang University-SCIENCE B, 2006)

Genetic Differences between Wild and Artificial Populations of Metasequoia glyptostroboides : Implications for Species Recovery - YUAN‐YUAN LI; XIAO‐YONG CHEN; XIN ZHANG; TIAN‐YI WU; HUI‐PING LU; YUE‐WEI CAI (Conservation Biology, 2005)
Information on population genetics is fundamental to developing in situ or ex situ conservation strategies. Few researchers, however, have compared the genetic structure of restored and natural populations of threatened plant species. Metasequoia glyptostroboides Hu & Cheng (dawn redwood) (Taxodiaceae), a living fossil endemic to China, may be the most successfully recovered threatened species, with many more individuals and a much wider distribution than fossil records indicate. We used random amplification of polymorphic DNA markers to compare the genetic structure of artificial populations with that of wild ones and to determine whether the genetic structure of M. glyptostroboides has been recovered as has its distribution. The genetic variation of wild populations of M. glyptostroboides was lower than the average of gymnosperms, indicating the effects of glaciations and recent habitat loss and fragmentation. Genetic variation in artificial populations was less, but not substantially, compared with wild populations. The unweighted pair group method with arithmetic mean revealed that the wild and the artificial populations formed two distinct groups. Artificial populations were more similar to each other (mean Nei's genetic distance = 0.0924) than to wild populations (mean distance = 0.2054). This might be the result of biased seed collection, vegetative propagation, or a mixture of propagules from different populations and an ultimate propagule source. These results suggest that although the quantity and distribution range have been successfully restored, the genetic structure of M. glyptostroboides has not recovered appropriately, given the loss of genetic variation and biased genetic composition in artificial populations. Therefore, in addition to protecting the wild populations, additional ex situ genetic reserves should be established based on genetic knowledge and via appropriate approaches. We suggest that population genetic and demographic indices should be considered when downlisting or delisting threatened species.

Crystal structure studies on rubrerythrin: enzymatic activity in relation to the zinc movement - Mei Li; Ming-yih Liu; Jean LeGall; Lu-lu Gui; Jun Liao; Tao Jiang; Ji-ping Zhang; Dong-cai Liang; Wen-rui Chang (JBIC Journal of Biological Inorganic Chemistry, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)